Mechanistic insight into insect declines is crucial for effective conservation - Benoit Guénard; Taylor A Bogar; Roger H Lee; Chi Man Leong; Runxi Wang; Mark KL Wong (Current Opinion in Insect Science, 2026)

Planktivorous fishes withstand 20 years of major coral cover oscillations - Mathieu Reynaud; Tom Garine-Wichatitsky; Renato A. Morais; Valeriano Parravicini; Fabien Morat; Benoit Pujol (Coral Reefs, 2026)

Spatial Distribution of Sediment Pesticides Concentrations in Streams of the Maritime Region of Canada - Benoit A. Lalonde (Bulletin of Environmental Contamination and Toxicology, 2026)
This study measured pesticide concentrations at 51 sites in streams in three maritime provinces of Canada in 2020–2021. There were 50 pesticides analysed in each sediment samples. Most of those pesticides had concentrations below the detection limit of the laboratory. However, nine pesticides had detections that ranged from one to nine sites. Terbufos and parathion were the two most detected pesticides of this study. Surprisingly, terbufos has not been registered for use in Canada since 2012 which showcases the prevalence of some legacy contamination in sediments. Furthermore, the concentrations of terbufos, chlorpyrifos and clothianidin exceeded the calculated sediment threshold which indicates the potential for ecological harm. The results align with other recent research, suggesting that pesticide occurrence in sediment is complex and not explained by a single factor like organic matter or chemical properties alone. Instead, it is a result of multiple interacting factors, including land use, the pesticide’s solubility, its concentration in the surrounding water, and the persistence of legacy products.

Beetle communities in agricultural landscapes: relative influences of climate, landscape, plant communities and agricultural practices - B. Penel; L. Genty; C. Marty; A. Bourdonné; A.-L. Clamens; L. Benoit; L. Soldati; A. Migeon; G.J. Kergoat; J. Haran; G. Fried; C.N. Meynard (Agriculture, Ecosystems & Environment, 2026)

Microbial Ecology of Mixotrophic Chain Elongation: Megasphaera spp. as Drivers of Medium‐Chain Carboxylate Production From H 2 , CO 2 , and Carboxylates - Grégoire B. L. Henry; Julien Tremblay; Benoit A. Stenuit; Patrick A. Gerin (Environmental Microbiology, 2026)
The production of medium‐chain carboxylates (MCC) by mixed culture fermentation of complex organic feedstocks is often constrained by the availability of reducing equivalents. Therefore, mixotrophic fermentation processes, which integrate diverse carbon and reducing equivalents sources, are gaining more attention. However, the microbial communities evolving in such complex environments, where organic and inorganic substrates interact, remain insufficiently understood. To identify the key microorganisms involved in mixotrophic MCC production, two bioreactors were initially fed with brewer's spent grain as organic feedstock and supplemented daily with H 2 and CO 2 as inorganic substrates. Time‐course analyses of net metabolite production rates and microbial community composition identified Megasphaera spp. (likely M. elsdenii and M. hexanoica ) as the main chain elongators in the system. The results suggest that these Megasphaera species metabolize short‐chain carboxylates, H 2 and CO 2 , with potential cross‐feeding interactions with acetogens (likely Clostridium ljungdahlii and Clostridium luticellarii ). The homoacetogenic acetate produced is subsequently elongated, likely by Megasphaera species, using H 2 and CO 2 as electron and carbon sources for production of elongated carboxylates. This study paves the way for the development of MCC production strategies that integrate organic waste valorization with direct CO 2 utilization, using H 2 as an electron donor, a process that aligns with low‐carbon‐footprint technologies.

Muigaia, a new Paleotropical genus of Convolvulaceae - Simon Wachira Ngima; Vivian Kathambi; Samuel Paul Kagame; Sushant More; Lauren A. Eserman; Rafael Felipe de Almeida; Benoit Loeuille; Marc S. M. Sosef; Patrick Chalo Mutiso; Higor Antonio-Domingues; Lars W. Chatrou; Ana Rita Simões (Kew Bulletin, 2026)
Summary A new genus of Convolvulaceae, Muigaia , is here proposed and fully revised, including molecular phylogenetic analyses, comprehensive morphological and palynological descriptions, identification keys, distribution maps and conservation assessments. It is a strictly paleotropical genus, occurring in Tropical Africa, Madagascar, India and Australia, and remarkably absent from the Malesian region. It is distinctive for the markedly angular stems; deeply palmately lobed, irregularly dissected leaves; leaf-like stipules at the base of the petiole; muricate, verrucose or cristate sepals; a 3-globose stigma and a 6-valved capsule. A revision of the species involved in this complex has resulted in the recognition of a total of seven species, including five new combinations, one new name ( M. shimpalei ) and one newly described species ( M. australiana ), endemic to Australia. The tropical African specimens of M. coptica , in particular, exhibit a wide range of morphological variation and should be investigated in detail. We expect that, now that Muigaia has been phylogenetically and morphologically circumscribed, further revisionary studies could focus on improving the species delimitation, and likely result in the discovery of additional new species to science.

Continental Contrasts in Climate Extremes That Control Tree Fecundity - James S. Clark; Robert Andrus; Margarita Arianoutsou; Davide Ascoli; Yves Bergeron; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; J. Julio Camarero; et al. (Global Change Biology, 2026)
In 2023, more than half of olive harvests ( Olea europaea ) across Spain, Greece, and Türkiye were lost to drought. The same year late freeze destroyed 90% of the peach crop ( Prunus persica ) on the Georgia Piedmont and the apple crop ( Malus domestica ) in central New York, Vermont, and southern Quebec. Climate extremes now rank with the costliest threats to agriculture, but their role in forest recovery from diebacks that are happening globally is unknown for lack of tree fecundity estimates in forests. Tolerance of climate extremes could depend on past exposure but constrained by phylogenetic conservatism. We report a continental scale analysis of climate extremes and forest fecundity across North America and Europe showing that responses to late freeze and drought are happening now. Species differences are not explained by the traits typically included in ecological studies and they are weakly associated with phylogeny. Late freeze, that is, freezing temperatures that follow the onset of flower development in spring, is shown to be “normal” in North America, but not Europe, potentially explaining failed seed production due to delayed onset and the resultant shorter growing period by North American transplants dating back at least to the 18th century. Drought has thus far had the greatest impacts in dry forested regions, but here too, species differences are not explained by traditional trait values. If responses have been buffered from drought and late freeze by past exposure, acclimation and local adaptation prove inadequate as extremes intensify.

Atlantic-wide connectivity of Ascension Island green turtles revealed by finer-scale mitochondrial DNA markers - Sophia A. Coveney; Eva Jiménez-Guri; Samantha Ball; Nathalie Mianseko; Annette C. Broderick; Brendan J. Godley; Joana M. Hancock; Welton Quirino Pereira; Aissa Regalla; Rita Gomes Rocha; Cheibani Senhoury; Benoit de Thoisy; et al. (Conservation Genetics, 2025)
Marine turtles undertake long migrations across different geographies and habitats, exposing them to a wide range of threats throughout their lifespan. Analysing population structure and connectivity is key to informing effective conservation management. We expand knowledge of Atlantic-wide connectivity of green turtles ( Chelonia mydas ) by characterising the genetic structure of the Ascension Island nesting population, one of the largest in the Atlantic Ocean, and carrying out Atlantic population structure and mixed stock analyses using high-resolution genetic markers. We amplified a ~ 738 bp fragment (extended D-loop) and a highly polymorphic mitochondrial short tandem repeat (mtSTR) fragment of the mitochondrial DNA control region, designating haplotypes based on (1) extended D-loop and (2) the extended D-loop and mtSTR combined. Overall, 11 extended D-loop and 33 combined haplotypes were found, the dominant haplotypes being CM-A8.1 and CM-A8.1/7-12-4-4. Population structure analysis found three main genetic groups: Northwest Atlantic, Northern South America, and South and East Atlantic. Mixed stock analyses indicate Ascension Island as a major source for juvenile foraging aggregations in the Southwest Atlantic (34–55%) and Central Africa (18–78%), with some contribution to West Africa (3–20%). Green turtles are vulnerable to fishery bycatch in the coastal waters of the South and East Atlantic. Our study underlines how improving sample sizes of Atlantic mtSTR haplotypes could further elucidate green turtle connectivity across threatened regions. We urge international collaboration to minimise mtSTR data gaps, in order to enhance connectivity assessments and improve conservation measures between countries that share populations.

Susceptibility of Lion’s paw scallop (Nodipecten subnodosus) juveniles to a pirAB-positive Vibrio campbellii strain isolated from Litopenaeus vannamei shrimp affected by Acute Hepatopancreatic Necrosis Disease (AHPND) - Krizia Pretell Monzón; Damaris Esquén Bayona; Yuriko Saavedra Ríos; Frank Guzman Escudero; Judith Villano Arango; Carlos A. Amasifuen Guerra; Cristina Escobedo Fregoso; Edouard Kraffe; Rosa Cueto Vega; Benoit Diringer (Journal of Invertebrate Pathology, 2025)

Methanol on red TNOs: A link between early composition and irradiation history - E. Hénault; D. Baklouti; R. Brunetto; Z. Djouadi; R.G. Urso; P. Benoit-Lamaitrie; J. Bourçois; O. Mivumbi; C.M. Dalle Ore; A. Ricca (Icarus, 2025)

Role of viral coinfection in post-pandemic invasive Group A streptococcal infections in adults, a nation-wide cohort study (iGASWISS) - S. Musumeci; A. MacPhail; M. Weisser Rohacek; A. Erba; D. Goldenberger; C. Lang; E. Colin-Benoit; S. L. Leib; P. Sendi; C. Chuard; V. Erard; C. Fournier; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2025)
Objective During the winter season of 2022–2023, numerous countries experienced a surge in invasive Streptococcus pyogenes (iGAS) infections. The role of viral coinfections in the post-COVID surge has not been elucidated. We report nation-wide data describing clinical presentation, microbiological characteristics, and associations with viral infection in adults during this period. Methods A multicenter retrospective cohort study was conducted across 10 hospitals in Switzerland, including adults (> 16 years old) with iGAS infection from November 2022 to February 2023. Descriptive analysis was performed. A multivariable logistic regression model was fitted to assess the impact of viral coinfection. In addition, genetic analysis was performed in available isolates. Results A total of 194 patients were included, with a median age of 50 years (interquartile range [IQR]: 37–69). 17/194 (8.8%) were immunosuppressed and 40/194 (20.6%) exhibited concomitant viral infections, predominantly Influenza A (21/40, 53%). Illness severity was high: 65/194 (33.5%) of cases necessitated admission to an intensive care unit (ICU), and the 30-day mortality was 4% ( n = 8). Among the available strains for genetic analysis ( n = 48), heterogeneity was found although ST28- emm 1 isolates (also known as M1UK) was predominant (22/48). Conclusion The post-COVID iGAS surge in Switzerland was associated with high levels of morbidity and mortality in immunocompetent adults. M1UK was predominant within the iGAS strains circulating in Switzerland during the study period and viral coinfection was a predictor for ICU admission and mortality.

Plant Trait Matching Occurs in Facilitative Interactions Across Global Drylands - Imke C. Smit; Peter C. le Roux; Santiago Soliveres; Nicolas Gross; Yoann Le Bagousse‐Pinguet; Hugo Saiz; Mehdi Abedi; Rodrigo Ahumada; Antonio I. Arroyo; Sergio Asensio; Richard Benoit; Niels Blaum; et al. (Global Ecology and Biogeography, 2025)
Aim Plant functional traits can influence interaction outcomes between nurse and target plants through a “functional trait match”, which occurs when the traits of nurse plants ameliorate their environment, and target plants possess traits that allow them to benefit from this ameliorated environment. We investigated how the traits of putative nurse species affect interaction outcomes across global drylands and determined the functional match that promotes facilitation. We also investigated how grazing pressure and global climatic and edaphic gradients affected this trait match. Location Global drylands. Time Period 2016–2019. Major Taxa Studied Vascular plants. Methods We used a collaborative survey conducted across 29 sites from five continents, where we gathered in situ co‐occurrences of dominant species (‘nurses’) and other vascular plant species, as well as their functional traits [plant height and leaf dry matter content (LDMC)]. Climate, edaphic variables and grazing pressure were measured in situ or extracted from databases. We used a model building approach to determine the effect of dominant plant traits on interaction outcomes, and how the functional trait match between nurse and target species is affected by environmental variables. Results Tall dominant plants with conservative leaves generally had a greater positive effect on species richness and cover beneath their canopies, but these effects were strongly modulated by grazing pressure and soil pH. Target plants that were significantly associated with dominant plants tended to be shorter, and have more acquisitive leaves than dominant plants, regardless of environmental conditions. However, the difference in height and LDMC between dominant plants and negatively associated target plants was strongly affected by environmental conditions. Main Conclusions Functional traits play a significant role in determining interaction outcomes between dryland plants. Facilitation in drylands is driven by a conservative‐acquisitive trait match, a pattern observed regardless of grazing pressure, climate and soil conditions.

tRNA expression and modifications as critical components in the biology of blood-feeding arthropods - Melissa Kelley; Patrick A Limbach; Joshua B Benoit (Current Opinion in Insect Science, 2025)

P31-24 Pharmacological validation of integrated nerve conduction velocity assays, functional observational battery and videotracking in the rat using peripheral nerve toxicants - A. Chefdeville; C. Bory; M. Terasse; V. Benoit; M. Latzko; N. Sadekova; A. Brown; S. Baudet (Toxicology Letters, 2025)

gSeaGen code by KM3NeT: An efficient tool to propagate muons simulated with CORSIKA - S. Aiello; A. Albert; A.R. Alhebsi; M. Alshamsi; S. Alves Garre; A. Ambrosone; F. Ameli; M. Andre; L. Aphecetche; M. Ardid; S. Ardid; H. Atmani; et al. (Computer Physics Communications, 2025)

Thermal tolerance of Aedes aegypti mosquito eggs is associated with urban adaptation and human interactions - Souvik Chakraborty; Emily Zigmond; Sher Shah; Diya Dayal; Massamba Sylla; Jewelna Akorli; Sampson Otoo; Noah H. Rose; Carolyn S. McBride; Peter A. Armbruster; Joshua B. Benoit (Journal of Thermal Biology, 2025)

Amino acid analysis using multiple time point hydrolysis and non-linear regression for determination of amino acid profiles and 21-hour correction factors of biological standards, and dairy cattle milk, tissue, rumen microbes, and various feeds - Andres F. Ortega; Joyce L. Marumo; Rebecca Coombe; Alexandria C. Benoit; Deborah A. Ross; Michael E. Van Amburgh (Animal Feed Science and Technology, 2025)

Advancing ocean monitoring and knowledge for societal benefit: the urgency to expand Argo to OneArgo by 2030 - Virginie Thierry; Hervé Claustre; Orens Pasqueron de Fommervault; Nathalie Zilberman; Kenneth S. Johnson; Brian A. King; Susan E. Wijffels; Udaya T. V. S. Bhaskar; Magdalena Alonso Balmaseda; Mathieu Belbeoch; Marine Bollard; Jacqueline Boutin; et al. (Frontiers in Marine Science, 2025)
The ocean plays an essential role in regulating Earth’s climate, influencing weather conditions, providing sustenance for large populations, moderating anthropogenic climate change, encompassing massive biodiversity, and sustaining the global economy. Human activities are changing the oceans, stressing ocean health, threatening the critical services the ocean provides to society, with significant consequences for human well-being and safety, and economic prosperity. Effective and sustainable monitoring of the physical, biogeochemical state and ecosystem structure of the ocean, to enable climate adaptation, carbon management and sustainable marine resource management is urgently needed. The Argo program, a cornerstone of the Global Ocean Observing System (GOOS), has revolutionized ocean observation by providing real-time, freely accessible global temperature and salinity data of the upper 2,000m of the ocean (Core Argo) using cost-effective simple robotics. For the past 25 years, Argo data have underpinned many ocean, climate and weather forecasting services, playing a fundamental role in safeguarding goods and lives. Argo data have enabled clearer assessments of ocean warming, sea level change and underlying driving processes, as well as scientific breakthroughs while supporting public awareness and education. Building on Argo’s success, OneArgo aims to greatly expand Argo’s capabilities by 2030, expanding to full-ocean depth, collecting biogeochemical parameters, and observing the rapidly changing polar regions. Providing a synergistic subsurface and global extension to several key space-based Earth Observation missions and GOOS components, OneArgo will enable biogeochemical and ecosystem forecasting and new long-term climate predictions for which the deep ocean is a key component. Driving forward a revolution in our understanding of marine ecosystems and the poorly-measured polar and deep oceans, OneArgo will be instrumental to assess sea level change, ocean carbon fluxes, acidification and deoxygenation. Emerging OneArgo applications include new views of ocean mixing, ocean bathymetry and sediment transport, and ecosystem resilience assessment. Implementing OneArgo requires about $100 million annually, a significant increase compared to present Argo funding. OneArgo is a strategic and cost-effective investment which will provide decision-makers, in both government and industry, with the critical knowledge needed to navigate the present and future environmental challenges, and safeguard both the ocean and human wellbeing for generations to come.

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Designing Sortable Guilds for Multispecies Selective Fish Passage - David M. Benoit; Daniel P. Zielinski; Reid G. Swanson; Donald A. Jackson; Robert L. McLaughlin; Theodore R. Castro‐Santos; R. Andrew Goodwin; Thomas C. Pratt; Andrew M. Muir (Fish and Fisheries, 2025)
The importance of connectivity for freshwater organisms is widely recognised, yet in‐stream barriers associated with population declines and increased risk of extinction remain globally ubiquitous. Despite their negative consequences, these barriers can protect aquatic communities by limiting the spread of invasive species, leading to conflicting management goals in some regions. Selective fish passage is a solution for the conflicting goals of passing native, desirable species while restricting the spread of invasives. Approaches that can target groups of species sharing similar attributes (i.e. guilds) are likely to be more efficient than those that target species individually, particularly in taxonomically diverse systems. We explored the guild structure of 220 Great Lakes freshwater fishes based on morphological, phenological, physiological and behavioural attributes associated with passage and movement. We identified five distinct guilds as well as the attributes most important for defining these groupings: maximum total length, trophic level, relative eye size, spawning temperature, spawning season, presence/absence of ampullary electroreceptors and the presence/absence of hearing specialisations. The approaches outlined in this work can be generalised to enhance selective fish passage in aquatic ecosystems worldwide.

GRANDlib: A simulation pipeline for the Giant Radio Array for Neutrino Detection (GRAND) - R. Alves Batista; A. Benoit-Lévy; T. Bister; M. Bohacova; M. Bustamante; W. Carvalho; Y. Chen; L. Cheng; S. Chiche; J.M. Colley; P. Correa; N. Cucu Laurenciu; et al. (Computer Physics Communications, 2025)

Life history stage effects on alert and flight initiation distances in king penguins (Aptenodytes patagonicus) - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2025)

Comparative pollinator conservation potential of coffee agroforestry relative to coffee monoculture and tropical rainforest in the DR Congo - Jonas Depecker; Filip Vandelook; Kurt Jordaens; Achik Dorchin; Benjamin Ntumba Katshela; Ieben Broeckhoven; Benoit Dhed’a; Arne Devriese; Lien Deckers; Piet Stoffelen; Olivier Honnay (Agriculture, Ecosystems & Environment, 2025)

Scaling up ocean conservation through recognition of key biodiversity areas in the Southern Ocean from multispecies tracking data - Sarah L. Becker; Charlotte Boyd; Jonathan M. Handley; Ben Raymond; Ryan Reisinger; Yan Ropert‐Coudert; Nora Apelgren; Tammy E. Davies; Mary‐Anne Lea; Mercedes Santos; Philip N. Trathan; Anton P. Van de Putte; et al. (Conservation Biology, 2025)
Biodiversity is critical for maintaining ecosystem function but is threatened by increasing anthropogenic pressures. In the Southern Ocean, a highly biologically productive region containing many endemic species, proactive management is urgently needed to mitigate increasing pressures from fishing, climate change, and tourism. Site‐based conservation is one important tool for managing the negative impacts of human activities on ecosystems. The Key Biodiversity Area (KBA) Standard is a standardized framework used to define sites vital for the persistence of global biodiversity based on criteria and quantitative thresholds. We used tracking data from 14 species of Antarctic and subantarctic seabirds and pinnipeds from the publicly available Retrospective Analysis of Antarctic Tracking Data (RAATD) data set to define KBAs for a diverse suite of marine predators. We used track2kba, an R package that supports identification of KBAs from telemetry data through identification of highly used habitat areas and estimates of local abundance within sites. We compared abundance estimates at each site with thresholds for KBA criteria A1, B1, and D1 (related to globally threatened species, individual geographically restricted species, and demographic aggregations, respectively). We identified 30 potential KBAs for 13 species distributed throughout the Southern Ocean that were vital for each individual species, population, and life‐history stage for which they were determined. These areas were identified as highly used by these populations based on observational data and complement the ongoing habitat modeling and bioregionalization work that has been used to prioritize conservation areas in this region. Although further work is needed to identify potential KBAs based on additional current and future data sets, we highlight the benefits of utilizing KBAs as part of a holistic approach to marine conservation, given their significant value as a global conservation tool.

Trends and Variability in Earth’s Energy Imbalance and Ocean Heat Uptake Since 2005 - Maria Z. Hakuba; Sébastien Fourest; Tim Boyer; Benoit Meyssignac; James A. Carton; Gaël Forget; Lijing Cheng; Donata Giglio; Gregory C. Johnson; Seiji Kato; Rachel E. Killick; Nicolas Kolodziejczyk; et al. (Surveys in Geophysics, 2024)
Earth’s energy imbalance (EEI) is a fundamental metric of global Earth system change, quantifying the cumulative impact of natural and anthropogenic radiative forcings and feedback. To date, the most precise measurements of EEI change are obtained through radiometric observations at the top of the atmosphere (TOA), while the quantification of EEI absolute magnitude is facilitated through heat inventory analysis, where ~ 90% of heat uptake manifests as an increase in ocean heat content (OHC). Various international groups provide OHC datasets derived from in situ and satellite observations, as well as from reanalyses ingesting many available observations. The WCRP formed the GEWEX-EEI Assessment Working Group to better understand discrepancies, uncertainties and reconcile current knowledge of EEI magnitude, variability and trends. Here, 21 OHC datasets and ocean heat uptake (OHU) rates are intercompared, providing OHU estimates ranging between 0.40 ± 0.12 and 0.96 ± 0.08 W m −2 (2005–2019), a spread that is slightly reduced when unequal ocean sampling is accounted for, and that is largely attributable to differing source data, mapping methods and quality control procedures. The rate of increase in OHU varies substantially between − 0.03 ± 0.13 (reanalysis product) and 1.1 ± 0.6 W m −2 dec −1 (satellite product). Products that either more regularly observe (satellites) or fill in situ data-sparse regions based on additional physical knowledge (some reanalysis and hybrid products) tend to track radiometric EEI variability better than purely in situ-based OHC products. This paper also examines zonal trends in TOA radiative fluxes and the impact of data gaps on trend estimates. The GEWEX-EEI community aims to refine their assessment studies, to forge a path toward best practices, e.g., in uncertainty quantification, and to formulate recommendations for future activities.

Towards sustainable construction in Cameroon : impact of tropical plant fibers on the performance of compressed earth bricks - Fabien Betene Ebanda; Armel Edwige Mewoli; Abel Emmanuel Njom; Marius Tony Kibong; Pierre Marcel Anicet Noah; Benoit Ndiwé; Marie Josette Ndengue; Sandrine Olive Biloa Otiti; Jean Raymond Lucien Meva’a; Atangana Ateba (Innovative Infrastructure Solutions, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Cardiac electrical and functional activity following an outdoor cold-water swimming event - Victorien Faivre-Rampant; Corentin Hingrand; A. Mezanger; Eric Saloux; Pierre Ollitrault; Simon Alvado; Hervé Normand; Igor B. Mekjavic; Thibaud Collet; Benoit Mauvieux; Joffrey Drigny; Amir Hodzic (Journal of Thermal Biology, 2024)

Invertebrate and dinoflagellate marine toxins targeting signaling and key components of the skeletal neuromuscular system of vertebrates - Jordi Molgó; Aurélie Couesnon; Evelyne Benoit; Armen Zakarian; Denis Servent; J. Cesar Cardenas; Frédéric A. Meunier (Toxicon, 2024)

Habitat Provision Differs Across Subtidal Reefs Varying in Location Within the Estuarine Landscape - Alyssa Outhwaite; Benoit Lebreton; Terence A. Palmer; Jennifer Beseres Pollack (Estuaries and Coasts, 2024)
Although position within the estuarine landscape is known to influence structural characteristics and ecological functioning of many habitats, the influence of position on subtidal oyster reef characteristics and functioning is relatively understudied. This study assessed habitat provision by oysters and benthic macrofauna on subtidal bar and patch oyster reefs within the northwestern Gulf of Mexico estuary. Bar reefs had greater and more variable oyster density, biomass, and volume, as well as dead shell material, compared to patch reefs. Benthic macrofaunal community composition differed between reef types, with bar reefs hosting 11 × and 30 × higher biomass of Porcellanidae and Ampithoidae crustaceans, and patch reefs supporting 34 × and 47 × higher biomass of Eunicidae annelids and Leptocheliidae crustaceans. The environmental variables most highly correlated with macrofaunal communities on both bar and patch reefs were sediment chlorophyll- a , volume of dead oyster shells, and depth. Despite differences in structural characteristics and position within the estuarine landscape, subtidal oyster reefs are often managed as a single habitat type. Our findings emphasize the importance of considering location in oyster reef conservation and restoration efforts to better predict and optimize faunal provision outcomes.

The Relationship Between Maturation Size and Maximum Tree Size From Tropical to Boreal Climates - Valentin Journé; Michał Bogdziewicz; Benoit Courbaud; Georges Kunstler; Tong Qiu; Marie‐Claire Aravena Acuña; Davide Ascoli; Yves Bergeron; Daniel Berveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; et al. (Ecology Letters, 2024)
The fundamental trade‐off between current and future reproduction has long been considered to result in a tendency for species that can grow large to begin reproduction at a larger size. Due to the prolonged time required to reach maturity, estimates of tree maturation size remain very rare and we lack a global view on the generality and the shape of this trade‐off. Using seed production from five continents, we estimate tree maturation sizes for 486 tree species spanning tropical to boreal climates. Results show that a species' maturation size increases with maximum size, but in a non‐proportional way: the largest species begin reproduction at smaller sizes than would be expected if maturation were simply proportional to maximum size. Furthermore, the decrease in relative maturation size is steepest in cold climates. These findings on maturation size drivers are key to accurately represent forests' responses to disturbance and climate change.

Testing the deep‐sea glacial disturbance hypothesis as a cause of low, present‐day Norwegian Sea diversity and resulting steep latitudinal diversity gradient, using fossil records - Anna B. Jöst; Huai‐Hsuan M. Huang; Yuanyuan Hong; Chih‐Lin Wei; Henning A. Bauch; Benoit Thibodeau; Thomas M. Cronin; Hisayo Okahashi; Moriaki Yasuhara (Global Ecology and Biogeography, 2024)
Aim Within the intensively‐studied, well‐documented latitudinal diversity gradient, the deep‐sea biodiversity of the present‐day Norwegian Sea stands out with its notably low diversity, constituting a steep latitudinal diversity gradient in the North Atlantic. The reason behind this has long been a topic of debate and speculation. Most prominently, it is explained by the deep‐sea glacial disturbance hypothesis, which states that harsh environmental glacial conditions negatively impacted Norwegian Sea diversities, which have not yet fully recovered. Our aim is to empirically test this hypothesis. Specific research questions are: (1) Has deep‐sea biodiversity been lower during glacials than during interglacials? ( 2) Was there any faunal shift at the Mid‐Brunhes Event (MBE) when the mode of glacial–interglacial climatic change was altered? Location Norwegian Sea, deep sea (1819–2800 m), coring sites MD992277, PS1243, and M23352. Time period 620.7–1.4 ka (Middle Pleistocene–Late Holocene). Taxa studied Ostracoda (Crustacea). Methods We empirically test the deep‐sea glacial disturbance hypothesis by investigating whether diversity in glacial periods is consistently lower than diversity in interglacial periods. Additionally, we apply comparative analyses to determine a potential faunal shift at the MBE, a Pleistocene event describing a fundamental shift in global climate. Results The deep Norwegian Sea diversity was not lower during glacial periods compared to interglacial periods. Holocene diversity was exceedingly lower than that of the last glacial period. Faunal composition changed substantially between pre‐ and post‐MBE. Main conclusions These results reject the glacial disturbance hypothesis, since the low glacial diversity is the important precondition here. The present‐day‐style deep Norwegian Sea ecosystem was established by the MBE, more specifically by MBE‐induced changes in global climate, which has led to more dynamic post‐MBE conditions. In a broader context, this implies that the MBE has played an important role in the establishment of the modern polar deep‐sea ecosystem and biodiversity in general.

Neurophysiological and other features of working memory in older adults at risk for dementia - Rachel A. Patterson; Heather Brooks; Mina Mirjalili; Neda Rashidi-Ranjbar; Reza Zomorrodi; Daniel M. Blumberger; Corinne E. Fischer; Alastair J. Flint; Ariel Graff-Guerrero; Nathan Herrmann; James L. Kennedy; Sanjeev Kumar; et al. (Cognitive Neurodynamics, 2024)

CamTrapAsia : A dataset of tropical forest vertebrate communities from 239 camera trapping studies - Calebe P. Mendes; Wido R. Albert; Zachary Amir; Marc Ancrenaz; Eric Ash; Badrul Azhar; Henry Bernard; Jedediah Brodie; Tom Bruce; Elliot Carr; Gopalasamy Reuben Clements; Glyn Davies; et al. (Ecology, 2024)
Information on tropical Asian vertebrates has traditionally been sparse, particularly when it comes to cryptic species inhabiting the dense forests of the region. Vertebrate populations are declining globally due to land‐use change and hunting, the latter frequently referred as “defaunation.” This is especially true in tropical Asia where there is extensive land‐use change and high human densities. Robust monitoring requires that large volumes of vertebrate population data be made available for use by the scientific and applied communities. Camera traps have emerged as an effective, non‐invasive, widespread, and common approach to surveying vertebrates in their natural habitats. However, camera‐derived datasets remain scattered across a wide array of sources, including published scientific literature, gray literature, and unpublished works, making it challenging for researchers to harness the full potential of cameras for ecology, conservation, and management. In response, we collated and standardized observations from 239 camera trap studies conducted in tropical Asia. There were 278,260 independent records of 371 distinct species, comprising 232 mammals, 132 birds, and seven reptiles. The total trapping effort accumulated in this data paper consisted of 876,606 trap nights, distributed among Indonesia, Singapore, Malaysia, Bhutan, Thailand, Myanmar, Cambodia, Laos, Vietnam, Nepal, and far eastern India. The relatively standardized deployment methods in the region provide a consistent, reliable, and rich count data set relative to other large‐scale pressence‐only data sets, such as the Global Biodiversity Information Facility (GBIF) or citizen science repositories (e.g., iNaturalist), and is thus most similar to eBird. To facilitate the use of these data, we also provide mammalian species trait information and 13 environmental covariates calculated at three spatial scales around the camera survey centroids (within 10‐, 20‐, and 30‐km buffers). We will update the dataset to include broader coverage of temperate Asia and add newer surveys and covariates as they become available. This dataset unlocks immense opportunities for single‐species ecological or conservation studies as well as applied ecology, community ecology, and macroecology investigations. The data are fully available to the public for utilization and research. Please cite this data paper when utilizing the data.

Heliophysics Great Observatories and international cooperation in Heliophysics: An orchestrated framework for scientific advancement and discovery - Larry Kepko; Rumi Nakamura; Yoshifumi Saito; Angelos Vourlidas; Matthew G.G.T. Taylor; Cristina H. Mandrini; Xóchitl Blanco-Cano; Dibyendu Chakrabarty; Ioannis A. Daglis; Clezio Marcos De Nardin; Anatoli Petrukovich; Minna Palmroth; et al. (Advances in Space Research, 2024)

Modelling the occupancy of two bird species of conservation concern in a managed Acadian Forest landscape: Applications for forest management - Remus James; Joseph R. Bennett; Scott Wilson; Greg Adams; Ken McIlwrick; Marc J. Mazerolle; Emily Smenderovac; Kelly Honeyman; Tom Swystun; Benoit Hamel; Lisa A. Venier (Forest Ecology and Management, 2024)

Embedded software of the KM3NeT central logic board - S. Aiello; A. Albert; S. Alves Garre; Z. Aly; A. Ambrosone; F. Ameli; M. Andre; E. Androutsou; M. Anghinolfi; M. Anguita; L. Aphecetche; M. Ardid; et al. (Computer Physics Communications, 2024)

Salinity, mineralogy, porosity, and hydrodynamics as drivers of carbon burial in urban mangroves from a megacity - Laetitia Allais; Benoit Thibodeau; Nicole S. Khan; Sean A. Crowe; Stefano Cannicci; Christelle Not (Science of The Total Environment, 2024)

Modern human atlas ranges of motion and Neanderthal estimations - Carlos A. Palancar; Markus Bastir; Antonio Rosas; Pierre-Michel Dugailly; Stefan Schlager; Benoit Beyer (Journal of Human Evolution, 2024)

Enhancing Tree Performance Through Species Mixing: Review of a Quarter-Century of TreeDivNet Experiments Reveals Research Gaps and Practical Insights - Leen Depauw; Emiel De Lombaerde; Els Dhiedt; Haben Blondeel; Luis Abdala-Roberts; Harald Auge; Nadia Barsoum; Jürgen Bauhus; Chengjin Chu; Abebe Damtew; Nico Eisenhauer; Marina V. Fagundes; et al. (Current Forestry Reports, 2024)

Use of atmospheric tides to estimate the hydraulic conductivity of confined and semi-confined aquifers - Rémi Valois; Benoit Derode; Jean-Michel Vouillamoz; D. O. Valerie Kotchoni; M. A. Lawson; Gabriel C. Rau (Hydrogeology Journal, 2023)

Isotopic and biochemical trophic markers reveal the complexity of interactions at the base of pelagic food webs (Mediterranean sea) - Chia-Ting Chen; François Carlotti; Mireille Harmelin-Vivien; Yves Letourneur; Nicolas Savoye; Gaël Guillou; Benoit Lebreton; Javier A. Tesán-Onrubia; Aude Barani; Véronique Cornet; Loïc Guilloux; Anaïs Esposito; et al. (Marine Environmental Research, 2023)

Recent trends in engineering algae for biohydrogen production: State of art strategies - Vandana Vinayak; Vandana Sirotiya; Priyanka Khandelwal; Anshuman Rai; Dipak A. Jadhav; Arivalagan Pugazhendhi; Benoit Schoefs; Justine Marchand; Kyu-Jung Chae (Fuel, 2023)

Disentangling the “many-eyes”, “dilution effect”, “selfish herd”, and “distracted prey” hypotheses in shaping alert and flight initiation distance in a colonial seabird - Tracey L. Hammer; Pierre Bize; Benoit Gineste; Jean-Patrice Robin; René Groscolas; Vincent A. Viblanc (Behavioural Processes, 2023)

The maxillary canal of the titanosuchid Jonkeria (Synapsida, Dinocephalia) - Julien Benoit; Luke A. Norton; Sifelani Jirah (The Science of Nature, 2023)
The maxillary canal of the titanosuchid dinocephalian Jonkeria is described based on digitised serial sections. We highlight that its morphology is more like that of the tapinocephalid Moschognathus than that of Anteosaurus . This is unexpected given the similarities between the dentition of Jonkeria and Anteosaurus (i.e., presence of a canine) and the fact that the branching pattern of the maxillary canal in synapsids usually co-varies with dentition. Hypotheses to account for similarities between Jonkeria and Moschognathus (common ancestry, function in social signalling or underwater sensing) are discussed. It is likely that the maxillary canal carries a strong phylogenetic signal, here supporting the clade Tapinocephalia.

Is a dissipation half-life of 5 years for chlordecone in soils of the French West Indies relevant? - Pierre-Loïc Saaidi; Olivier Grünberger; Anatja Samouëlian; Yves Le Roux; Antoine Richard; Damien A. Devault; Cyril Feidt; Pierre Benoit; Olivier Evrard; Gwenaël Imfeld; Christophe Mouvet; Marc Voltz (Environmental Pollution, 2023)

Linking seed size and number to trait syndromes in trees - Michal Bogdziewicz; Marie‐Claire Aravena Acuña; Robert Andrus; Davide Ascoli; Yves Bergeron; Daniel Brveiller; Thomas Boivin; Raul Bonal; Thomas Caignard; Maxime Cailleret; Rafael Calama; Sergio Donoso Calderon; et al. (Global Ecology and Biogeography, 2023)
Aim Our understanding of the mechanisms that maintain forest diversity under changing climate can benefit from knowledge about traits that are closely linked to fitness. We tested whether the link between traits and seed number and seed size is consistent with two hypotheses, termed the leaf economics spectrum and the plant size syndrome, or whether reproduction represents an independent dimension related to a seed size–seed number trade‐off. Location Most of the data come from Europe, North and Central America and East Asia. A minority of the data come from South America, Africa and Australia. Time period 1960–2022. Major taxa studied Trees. Methods We gathered 12 million observations of the number of seeds produced in 784 tree species. We estimated the number of seeds produced by individual trees and scaled it up to the species level. Next, we used principal components analysis and generalized joint attribute modelling (GJAM) to map seed number and size on the tree traits spectrum. Results Incorporating seed size and number into trait analysis while controlling for environment and phylogeny with GJAM exposes relationships in trees that might otherwise remain hidden. Production of the large total biomass of seeds [product of seed number and seed size; hereafter, species seed productivity (SSP)] is associated with high leaf area, low foliar nitrogen, low specific leaf area (SLA) and dense wood. Production of high seed numbers is associated with small seeds produced by nutrient‐demanding species with softwood, small leaves and high SLA. Trait covariation is consistent with opposing strategies: one fast‐growing, early successional, with high dispersal, and the other slow‐growing, stress‐tolerant, that recruit in shaded conditions. Main conclusions Earth system models currently assume that reproductive allocation is indifferent among plant functional types. Easily measurable seed size is a strong predictor of the seed number and species seed productivity. The connection of SSP with the functional traits can form the first basis of improved fecundity prediction across global forests.

Corrigendum: Ten lessons on the resilience of the EU common fisheries policy towards climate change and fuel efficiency - A call for adaptive, flexible and well-informed fisheries management - Francois Bastardie; David A. Feary; Thomas Brunel; Laurence T. Kell; Ralf Döring; Sebastien Metz; Ole R. Eigaard; Oihane C. Basurko; Valerio Bartolino; Jacob Bentley; Benoit Berges; Sieme Bossier; et al. (Frontiers in Marine Science, 2023)

Development of a GNSS/INS buoy array in preparation for SWOT validation in Bass Strait - Boye Zhou; Christopher Watson; Jack Beardsley; Benoit Legresy; Matt A. King (Frontiers in Marine Science, 2023)
In preparation for validation of the swath-based altimetry mission (Surface Water Oceanography Topography, SWOT), we developed a buoy array, equipped with Global Navigation Satellite System/Inertial Navigation System, capable of accurately observing sea surface height (SSH), wave information and tropospheric delay. Here we present results from an 8-day trial deployment at five locations along a Sentinel-6 Michael Freilich (S6MF) ground track in Bass Strait. A triplet buoy group including two new buoys (Mk-VI) and a single predecessor (Mk-IV) were deployed in proximity to the historic Jason-series comparison point. SSH solutions compared against an in-situ mooring suggest the new buoys were working at an equivalent precision of ~1.5 cm to the previous design (MK-IV). At 10-km spacing along the S6MF track, the buoy array was shown to observe the progression of oceanographic and meteorological phenomena. Tidal analysis of the buoy array indicated moderate spatial variability in the shallow water tidal constituents, with differences in the instantaneous tidal height of up to ~0.2 m across the 40-km track. Further, tidal resonance within Bass Strait was observed to vary, most probably modulated by atmospheric conditions, yet only partially captured by an existing dynamic atmospheric correction product. A preliminary investigation into the spatial scale of the buoy error based on observed/inferred geostrophic currents with our present buoy array configuration suggests that the signal-noise ratio of the array became significant at 20-km spacing in Bass Strait. Finally, as an illustrative comparison between the buoy array and high resolution S6MF data, a single cycle was compared. The wet tropospheric delay observed by the S6MF radiometer exhibited some potential land contamination in the deployed area, while the 1-Hz and 20-Hz significant wave height from S6MF appeared within mission requirements. Generally good agreement between buoy and altimeter SSH was observed. However, subtle differences between the altimeter and the buoy sea level anomaly series warrants further investigation with additional cycles from a sustained deployment in the area. We conclude that the buoy array offers a useful geodetic tool to help quantify and understand intra-swath variability in the context of the SWOT mission.

Modifying the diets of captive proboscis monkeys in a temperate zoo to reduce weight loss and renal disease - Satoru Hoshino; Satoru Seino; Akinori Azumano; Augustine Tuuga; Senthilvel K. S. S. Nathan; Diana A. Ramirez Saldivar; Benoit Goossens; Milena Salgado-Lynn; Ikki Matsuda; Masato Yayota (Primates, 2023)

Carboxypeptidase U (TAFIa) Is Rapidly Activated and Deactivated Following Thrombolysis and Thrombectomy in Stroke Patients - Joachim C. Mertens; Vanessa Blanc-Guillemaud; Karen Claesen; Pere Cardona; Dirk Hendriks; Benoit Tyl; Carlos A. Molina (Translational Stroke Research, 2022)

Oceanic giants dance to atmospheric rhythms: Ephemeral wind‐driven resource tracking by blue whales - John P. Ryan; Kelly J. Benoit‐Bird; William K. Oestreich; Paul Leary; Kevin B. Smith; Chad M. Waluk; David E. Cade; James A. Fahlbusch; Brandon L. Southall; John E. Joseph; Tetyana Margolina; John Calambokidis; et al. (Ecology Letters, 2022)
Trophic transfer of energy through marine food webs is strongly influenced by prey aggregation and its exploitation by predators. Rapid aggregation of some marine fish and crustacean forage species during wind‐driven coastal upwelling has recently been discovered, motivating the hypothesis that predators of these forage species track the upwelling circulation in which prey aggregation occurs. We examine this hypothesis in the central California Current Ecosystem using integrative observations of upwelling dynamics, forage species' aggregation, and blue whale movement. Directional origins of blue whale calls repeatedly tracked upwelling plume circulation when wind‐driven upwelling intensified and aggregation of forage species was heightened. Our findings illustrate a resource tracking strategy by which blue whales may maximize energy gain amid ephemeral foraging opportunities. These findings have implications for the ecology and conservation of diverse predators that are sustained by forage populations whose behaviour is responsive to episodic environmental dynamics.

Ten lessons on the resilience of the EU common fisheries policy towards climate change and fuel efficiency - A call for adaptive, flexible and well-informed fisheries management - Francois Bastardie; David A. Feary; Thomas Brunel; Laurence T. Kell; Ralf Döring; Sebastien Metz; Ole R. Eigaard; Oihane C. Basurko; Valerio Bartolino; Jacob Bentley; Benoit Berges; Sieme Bossier; et al. (Frontiers in Marine Science, 2022)
To effectively future-proof the management of the European Union fishing fleets we have explored a suite of case studies encompassing the northeast and tropical Atlantic, the Mediterranean, Baltic and Black Seas. This study shows that European Union (EU) fisheries are likely resilient to climate-driven short-term stresses, but may be negatively impacted by long-term trends in climate change. However, fisheries’ long-term stock resilience can be improved (and therefore be more resilient to increasing changes in climate) by adopting robust and adaptive fisheries management, provided such measures are based on sound scientific advice which includes uncertainty. Such management requires regular updates of biological reference points. Such updates will delineate safe biological limits for exploitation, providing both high long-term yields with reduced risk of stock collapse when affected by short-term stresses, and enhanced compliance with advice to avoid higher than intended fishing mortality. However, high resilience of the exploited ecosystem does not necessarily lead to the resilience of the economy of EU fisheries from suffering shocks associated with reduced yields, neither to a reduced carbon footprint if fuel use increases from lower stock abundances. Fuel consumption is impacted by stock development, but also by changes in vessel and gear technologies, as well as fishing techniques. In this respect, energy-efficient fishing technologies already exist within the EU, though implementing them would require improving the uptake of innovations and demonstrating to stakeholders the potential for both reduced fuel costs and increased catch rates. A transition towards reducing fuel consumption and costs would need to be supported by the setup of EU regulatory instruments. Overall, to effectively manage EU fisheries within a changing climate, flexible, adaptive, well-informed and well-enforced management is needed, with incentives provided for innovations and ocean literacy to cope with the changing conditions, while also reducing the dependency of the capture fishing industry on fossil fuels. To support such management, we provide 10 lessons to characterize ‘win-win’ fishing strategies for the European Union, which develop leverages in which fishing effort deployed corresponds to Maximum Sustainable Yield targets and Common Fisheries Policy minimal effects objectives. In these strategies, higher catch is obtained in the long run, less fuel is spent to attain the catch, and the fisheries have a higher resistance and resilience to shock and long-term factors to face climate-induced stresses.

Water table depth modulates productivity and biomass across Amazonian forests - Thaiane R. Sousa; Juliana Schietti; Igor O. Ribeiro; Thaise Emílio; Rafael Herrera Fernández; Hans ter Steege; Carolina V. Castilho; Adriane Esquivel‐Muelbert; Timothy Baker; Aline Pontes‐Lopes; Camila V. J. Silva; Juliana M. Silveira; et al. (Global Ecology and Biogeography, 2022)
Aim Water availability is the major driver of tropical forest structure and dynamics. Most research has focused on the impacts of climatic water availability, whereas remarkably little is known about the influence of water table depth and excess soil water on forest processes. Nevertheless, given that plants take up water from the soil, the impacts of climatic water supply on plants are likely to be modulated by soil water conditions. Location Lowland Amazonian forests. Time period 1971–2019. Methods We used 344 long‐term inventory plots distributed across Amazonia to analyse the effects of long‐term climatic and edaphic water supply on forest functioning. We modelled forest structure and dynamics as a function of climatic, soil‐water and edaphic properties. Results Water supplied by both precipitation and groundwater affects forest structure and dynamics, but in different ways. Forests with a shallow water table (depth Main conclusions We show that the two extremes of water availability (excess and deficit) both reduce productivity in Amazon upland ( terra‐firme ) forests. Biomass and productivity across Amazonia respond not simply to regional climate, but rather to its interaction with water table conditions, exhibiting high local differentiation. Our study disentangles the relative contribution of those factors, helping to improve understanding of the functioning of tropical ecosystems and how they are likely to respond to climate change.

Globally, tree fecundity exceeds productivity gradients - Valentin Journé; Robert Andrus; Marie‐Claire Aravena; Davide Ascoli; Roberta Berretti; Daniel Berveiller; Michal Bogdziewicz; Thomas Boivin; Raul Bonal; Thomas Caignard; Rafael Calama; Jesús Julio Camarero; et al. (Ecology Letters, 2022)
Lack of tree fecundity data across climatic gradients precludes the analysis of how seed supply contributes to global variation in forest regeneration and biotic interactions responsible for biodiversity. A global synthesis of raw seedproduction data shows a 250‐fold increase in seed abundance from cold‐dry to warm‐wet climates, driven primarily by a 100‐fold increase in seed production for a given tree size. The modest (threefold) increase in forest productivity across the same climate gradient cannot explain the magnitudes of these trends. The increase in seeds per tree can arise from adaptive evolution driven by intense species interactions or from the direct effects of a warm, moist climate on tree fecundity. Either way, the massive differences in seed supply ramify through food webs potentially explaining a disproportionate role for species interactions in the wet tropics.

Global maps of soil temperature - Jonas J. Lembrechts; Johan van den Hoogen; Juha Aalto; Michael B. Ashcroft; Pieter De Frenne; Julia Kemppinen; Martin Kopecký; Miska Luoto; Ilya M. D. Maclean; Thomas W. Crowther; Joseph J. Bailey; Stef Haesen; et al. (Global Change Biology, 2022)
Research in global change ecology relies heavily on global climatic grids derived from estimates of air temperature in open areas at around 2 m above the ground. These climatic grids do not reflect conditions below vegetation canopies and near the ground surface, where critical ecosystem functions occur and most terrestrial species reside. Here, we provide global maps of soil temperature and bioclimatic variables at a 1‐km 2 resolution for 0–5 and 5–15 cm soil depth. These maps were created by calculating the difference (i.e. offset) between in situ soil temperature measurements, based on time series from over 1200 1‐km 2 pixels (summarized from 8519 unique temperature sensors) across all the world's major terrestrial biomes, and coarse‐grained air temperature estimates from ERA5‐Land (an atmospheric reanalysis by the European Centre for Medium‐Range Weather Forecasts). We show that mean annual soil temperature differs markedly from the corresponding gridded air temperature, by up to 10°C (mean = 3.0 ± 2.1°C), with substantial variation across biomes and seasons. Over the year, soils in cold and/or dry biomes are substantially warmer (+3.6 ± 2.3°C) than gridded air temperature, whereas soils in warm and humid environments are on average slightly cooler (−0.7 ± 2.3°C). The observed substantial and biome‐specific offsets emphasize that the projected impacts of climate and climate change on near‐surface biodiversity and ecosystem functioning are inaccurately assessed when air rather than soil temperature is used, especially in cold environments. The global soil‐related bioclimatic variables provided here are an important step forward for any application in ecology and related disciplines. Nevertheless, we highlight the need to fill remaining geographic gaps by collecting more in situ measurements of microclimate conditions to further enhance the spatiotemporal resolution of global soil temperature products for ecological applications.

Transcriptomic modulation in response to high-intensity interval training in monocytes of older women with type 2 diabetes - Jovane Hamelin Morrissette; Dominic Tremblay; Alexis Marcotte-Chénard; Farah Lizotte; Marie A. Brunet; Benoit Laurent; Eléonor Riesco; Pedro Geraldes (European Journal of Applied Physiology, 2022)

Suction drainage fluid culture during septic orthopaedic surgery, a retrospective study - C.-A. Hobson; J. Lourtet-Hascoët; A. Mizrahi; N. El Helali; C. Couzigou; A. Mohamed Hadj; R. Courseau; G. Riouallon; F. Boillot; A. Le Monnier; P. Jouffroy; Benoit Pilmis (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Importance of Serpulid Reef to the Functioning of a Hypersaline Estuary - Terence A. Palmer; Natasha Breaux; Benoit Lebreton; Gaël Guillou; Jennifer Beseres Pollack (Estuaries and Coasts, 2022)

ATLANTIC ANTS: a data set of ants in Atlantic Forests of South America - Rogério R. Silva; Felipe Martello; Rodrigo Machado Feitosa; Otávio Guilherme M. Silva; Lívia Pires do Prado; Carlos Roberto F. Brandão; Emília Zoppas de Albuquerque; Maria Santina C. Morini; Jacques Hubert Charles Delabie; Erison Carlos dos Santos Monteiro; Agripino Emanuel Oliveira Alves; Alexander L. Wild; et al. (Ecology, 2022)
Ants, an ecologically successful and numerically dominant group of animals, play key ecological roles as soil engineers, predators, nutrient recyclers, and regulators of plant growth and reproduction in most terrestrial ecosystems. Further, ants are widely used as bioindicators of the ecological impact of land use. We gathered information of ant species in the Atlantic Forest of South America. The ATLANTIC ANTS data set, which is part of the ATLANTIC SERIES data papers, is a compilation of ant records from collections (18,713 records), unpublished data (29,651 records), and published sources (106,910 records; 1,059 references), including papers, theses, dissertations, and book chapters published from 1886 to 2020. In total, the data set contains 153,818 ant records from 7,636 study locations in the Atlantic Forest, representing 10 subfamilies, 99 genera, 1,114 ant species identified with updated taxonomic certainty, and 2,235 morphospecies codes. Our data set reflects the heterogeneity in ant records, which include ants sampled at the beginning of the taxonomic history of myrmecology (the 19th and 20th centuries) and more recent ant surveys designed to address specific questions in ecology and biology. The data set can be used by researchers to develop strategies to deal with different macroecological and region‐wide questions, focusing on assemblages, species occurrences, and distribution patterns. Furthermore, the data can be used to assess the consequences of changes in land use in the Atlantic Forest on different ecological processes. No copyright restrictions apply to the use of this data set, but we request that authors cite this data paper when using these data in publications or teaching events.

Regional Variation in Winter Foraging Strategies by Weddell Seals in Eastern Antarctica and the Ross Sea - Rob Harcourt; Mark A. Hindell; Clive R. McMahon; Kimberly T. Goetz; Jean-Benoit Charrassin; Karine Heerah; Rachel Holser; Ian D. Jonsen; Michelle R. Shero; Xavier Hoenner; Rose Foster; Baukje Lenting; et al. (Frontiers in Marine Science, 2021)
The relative importance of intrinsic and extrinsic determinants of animal foraging is often difficult to quantify. The most southerly breeding mammal, the Weddell seal, remains in the Antarctic pack-ice year-round. We compared Weddell seals tagged at three geographically and hydrographically distinct locations in East Antarctica (Prydz Bay, Terre Adélie , and the Ross Sea) to quantify the role of individual variability and habitat structure in winter foraging behaviour. Most Weddell seals remained in relatively small areas close to the coast throughout the winter, but some dispersed widely. Individual utilisation distributions ( UDi , a measure of the total area used by an individual seal) ranged from 125 to 20,825 km 2 . This variability was not due to size or sex but may be due to other intrinsic states for example reproductive condition or personality. The type of foraging (benthic vs. pelagic) varied from 56.6 ± 14.9% benthic dives in Prydz Bay through 42.1 ± 9.4% Terre Adélie to only 25.1 ± 8.7% in the Ross Sea reflecting regional hydrographic structure. The probability of benthic diving was less likely the deeper the ocean. Ocean topography was also influential at the population level; seals from Terre Adélie , with its relatively narrow continental shelf, had a core (50%) UD of only 200 km 2 , considerably smaller than the Ross Sea (1650 km 2 ) and Prydz Bay (1700 km 2 ). Sea ice concentration had little influence on the time the seals spent in shallow coastal waters, but in deeper offshore water they used areas of higher ice concentration. Marine Protected Areas (MPAs) in the Ross Sea encompass all the observed Weddell seal habitat, and future MPAs that include the Antarctic continental shelf are likely to effectively protect key Weddell seal habitat.

Freshwater inflow and responses from estuaries across a climatic gradient: An assessment of northwestern Gulf of Mexico estuaries based on stable isotopes - Danielle A. Marshall; Megan K. La Peyre; Terence A. Palmer; Gaël Guillou; Blair D. Sterba‐Boatwright; Jennifer Beseres Pollack; Benoit Lebreton (Limnology and Oceanography, 2021)
Estuaries exist across a large climatic gradient in the northwestern Gulf of Mexico, capturing a range of hydrologic conditions and estuarine functioning. We examined freshwater inflow, salinity, and stable isotope compositions (δ 13 C, δ 15 N) of oysters, suspended particulate organic matter (SPOM), and surface sediment organic matter (SSOM) from five estuaries across the hydrologic gradient. All five estuaries experienced large decreases in freshwater inflow over the last 40 yr, with three estuaries being subject to freshwater inflow reductions of more than 85%. Generally, these freshwater inflow decreases were associated with estuarine salinity increases. Across the spatial gradient, average salinity generally increased from northeast to southwest estuaries. SPOM in the northeastern, lower salinity estuaries generally contained more continental organic matter and was of higher quality (i.e., lower C/chlorophyll a ratio), as compared to southwestern, higher salinity estuaries. Similarly, both SSOM and oyster δ 13 C values were positively correlated with salinity, further highlighting that food webs in lower salinity estuaries are more greatly influenced by continental organic matter than those in higher salinity estuaries. A decrease in the connectivity between continental and coastal habitats may have broad consequences for flows of organic matter, and estuarine function and health. Conducting studies across large‐scale hydrologic gradients can provide a useful approach to informing and predicting shifts in estuarine functioning.

A re-assessment of the oldest therapsid Raranimus confirms its status as a basal member of the clade and fills Olson’s gap - A. Duhamel; J. Benoit; B. S. Rubidge; J. Liu (The Science of Nature, 2021)

Vertical migration timing illuminates the importance of visual and nonvisual predation pressure in the mesopelagic zone - Kelly J. Benoit‐Bird; Mark A. Moline (Limnology and Oceanography, 2021)
Each day, motile pelagic organisms of all sizes undergo vertical movements tied to sunset and sunrise. Diel migration of animals is thought to result from the competing need to feed in energy rich surface waters while avoiding visual predators. Previous study using a newly adapted autonomous vehicle to measure individual characteristics in scattering layers provided the first measures of the internal layer structure, demonstrating that deep scattering layers can be made up of many topologically scaled, mono‐specific aggregations, or “schools.” Follow‐up measurements presented here show these schools of mesopelagic animals remain coherent during upward migration at dusk. We found that groups of smaller animals began migrating sooner each night than larger individuals, consistent with their relatively lower detectability by visual predators. We also found a correlation with taxonomic differences in swimming capabilities, suggesting that the ability to avoid predators if they are encountered also plays a role in the patterns of migration observed. The presence of acoustic predators, Risso's dolphins ( Grampus griseus ), however, altered this pattern for their primary prey, causing squid to remain at depth for approximately 40 min longer than others. The risk of predation by this air‐breathing predator decreases with depth, making delaying migration an appropriate response to this largely nonvisual predation risk. Understanding the timing of individual migration patterns provides insights into the bioenergetic and predator–prey processes in the mesopelagic zone that are critical for understanding the ecological and biogeochemical impacts of these high biomass layers in the ocean.

Seeing through the static: the temporal dimension of plant–animal mutualistic interactions - Paul J. CaraDonna; Laura A. Burkle; Benjamin Schwarz; Julian Resasco; Tiffany M. Knight; Gita Benadi; Nico Blüthgen; Carsten F. Dormann; Qiang Fang; Jochen Fründ; Benoit Gauzens; Christopher N. Kaiser‐Bunbury; et al. (Ecology Letters, 2021)
Most studies of plant–animal mutualistic networks have come from a temporally static perspective. This approach has revealed general patterns in network structure, but limits our ability to understand the ecological and evolutionary processes that shape these networks and to predict the consequences of natural and human‐driven disturbance on species interactions. We review the growing literature on temporal dynamics of plant–animal mutualistic networks including pollination, seed dispersal and ant defence mutualisms. We then discuss potential mechanisms underlying such variation in interactions, ranging from behavioural and physiological processes at the finest temporal scales to ecological and evolutionary processes at the broadest. We find that at the finest temporal scales (days, weeks, months) mutualistic interactions are highly dynamic, with considerable variation in network structure. At intermediate scales (years, decades), networks still exhibit high levels of temporal variation, but such variation appears to influence network properties only weakly. At the broadest temporal scales (many decades, centuries and beyond), continued shifts in interactions appear to reshape network structure, leading to dramatic community changes, including loss of species and function. Our review highlights the importance of considering the temporal dimension for understanding the ecology and evolution of complex webs of mutualistic interactions.

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: part 2 - Julian J. Eaton-Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2020)

The Evolution of the Maxillary Canal in Probainognathia (Cynodontia, Synapsida): Reassessment of the Homology of the Infraorbital Foramen in Mammalian Ancestors - Julien Benoit; Irina Ruf; Juri A. Miyamae; Vincent Fernandez; Pablo Gusmão Rodrigues; Bruce S. Rubidge (Journal of Mammalian Evolution, 2020)

Activity niches outperform thermal physiological limits in predicting global ant distributions - Fengyi Guo; Benoit Guénard; Evan P. Economo; Curtis A. Deutsch; Timothy C. Bonebrake (Journal of Biogeography, 2020)
Aim Thermal physiology is commonly used in mechanistic models to predict species distribution and project distribution change. Such thermal constraints for ants are often measured under laboratory conditions as critical thermal limits (CT max and CT min ), but have also been observed in the field as foraging thermal limits (FT min and FT max ). Here we compared distribution projections based on ant physiological and behavioural thermal limits with their realized distributions to assess the validity of using ecophysiological models to predict species ranges over large scales. Location Global. Taxon Ants. Methods From published literature, we compiled a database of 148 lab‐measured critical thermal limits and 137 field‐observed foraging thermal limits for 20 ant genera distributed around the world. We projected their potential ranges using active hour thresholds by matching their thermal limits or preferred thermal breadth (incorporating thermal optima) with hourly surface temperature data. We then compared the projections against a comprehensive global database of ant distributions to assess the validity of physiologically and behaviourally based models. Results We found that surface temperature plays a clear role in generic‐level ant biogeography. Projections based on foraging thermal limits were more conservative in constraining ranges to observed distributions, while projections based on critical thermal limits often overestimated ranges. Furthermore, thermal limit models can be improved by incorporating behaviourally derived thermal optima. Main conclusions Our results suggest that temperature‐dependent activity niches and thermal optima better reveal species realized thermal niches than critical thermal limits, and hence can improve predictions of species distributions and future distribution changes under climate change.

Correction to: Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

Documenting lemming population change in the Arctic: Can we detect trends? - Dorothée Ehrich; Niels M. Schmidt; Gilles Gauthier; Ray Alisauskas; Anders Angerbjörn; Karin Clark; Frauke Ecke; Nina E. Eide; Erik Framstad; Jay Frandsen; Alastair Franke; Olivier Gilg; et al. (Ambio, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Compositional variations of chromian spinels from peridotites of the Spontang ophiolite complex, Ladakh, NW Himalayas, India: petrogenetic implications - Mallika K. Jonnalagadda; Nitin R. Karmalkar; Mathieu Benoit; Michel Gregoire; Raymond A. Duraiswami; Shivani Harshe; Sagar Kamble (Geosciences Journal, 2019)

The Antarctic mite, Alaskozetes antarcticus, shares bacterial microbiome community membership but not abundance between adults and tritonymphs - Christopher J. Holmes; Emily C. Jennings; J. D. Gantz; Drew Spacht; Austin A. Spangler; David L. Denlinger; Richard E. Lee; Trinity L. Hamilton; Joshua B. Benoit (Polar Biology, 2019)

The neutrophil to lymphocyte ratio indexes individual variation in the behavioural stress response of wild roe deer across fluctuating environmental conditions - Jeffrey Carbillet; Benjamin Rey; Typhaine Lavabre; Yannick Chaval; Joël Merlet; François Débias; Corinne Régis; Sylvia Pardonnet; Jeanne Duhayer; Jean-Michel Gaillard; A. J. M. Hewison; Jean-François Lemaître; et al. (Behavioral Ecology and Sociobiology, 2019)

Voluntary Restoration: Mitigation's Silent Partner in the Quest to Reverse Coastal Wetland Loss in the USA - Rachel K. Gittman; Christopher J. Baillie; Katie K. Arkema; Richard O. Bennett; Jeff Benoit; Seth Blitch; Julien Brun; Anthony Chatwin; Allison Colden; Alyssa Dausman; Bryan DeAngelis; Nathaniel Herold; et al. (Frontiers in Marine Science, 2019)

Measuring Global Ocean Heat Content to Estimate the Earth Energy Imbalance - Benoit Meyssignac; Tim Boyer; Zhongxiang Zhao; Maria Z. Hakuba; Felix W. Landerer; Detlef Stammer; Armin Köhl; Seiji Kato; Tristan L’Ecuyer; Michael Ablain; John Patrick Abraham; Alejandro Blazquez; et al. (Frontiers in Marine Science, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Animal-Borne Telemetry: An Integral Component of the Ocean Observing Toolkit - Rob Harcourt; Ana M. M. Sequeira; Xuelei Zhang; Fabien Roquet; Kosei Komatsu; Michelle Heupel; Clive McMahon; Fred Whoriskey; Mark Meekan; Gemma Carroll; Stephanie Brodie; Colin Simpfendorfer; et al. (Frontiers in Marine Science, 2019)

Extended-pulsed fidaxomicin versus vancomycin for Clostridium difficile infection: EXTEND study subgroup analyses - Oliver A. Cornely; Maria J. G. T. Vehreschild; Nicholas Adomakoh; Areti Georgopali; Andreas Karas; Gbenga Kazeem; Benoit Guery (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Biology and biotechnological applications of microalgae and photosynthetic prokaryotes: Part 1 - Julian J. Eaton‐Rye; Benoit Guieysse; Michael A. Packer; Tina C. Summerfield; Susanna A. Wood (New Zealand Journal of Botany, 2019)

Hippocampal LTP modulation and glutamatergic receptors following vestibular loss - B. Truchet; A. Benoit; F. Chaillan; P. F. Smith; B. Philoxene; M. Guillamin; B. Poucet; A. Coquerel; Stephane Besnard (Brain Structure and Function, 2019)

Nitrous oxide emissions from microalgae: potential pathways and significance - Maxence Plouviez; Andy Shilton; Michael A. Packer; Benoit Guieysse (Journal of Applied Phycology, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Dominance–diversity relationships in ant communities differ with invasion - Xavier Arnan; Alan N. Andersen; Heloise Gibb; Catherine L. Parr; Nathan J. Sanders; Robert R. Dunn; Elena Angulo; Fabricio B. Baccaro; Tom R. Bishop; Raphaël Boulay; Cristina Castracani; Xim Cerdá; et al. (Global Change Biology, 2018)
The relationship between levels of dominance and species richness is highly contentious, especially in ant communities. The dominance‐impoverishment rule states that high levels of dominance only occur in species‐poor communities, but there appear to be many cases of high levels of dominance in highly diverse communities. The extent to which dominant species limit local richness through competitive exclusion remains unclear, but such exclusion appears more apparent for non‐native rather than native dominant species. Here we perform the first global analysis of the relationship between behavioral dominance and species richness. We used data from 1,293 local assemblages of ground‐dwelling ants distributed across five continents to document the generality of the dominance‐impoverishment rule, and to identify the biotic and abiotic conditions under which it does and does not apply. We found that the behavioral dominance–diversity relationship varies greatly, and depends on whether dominant species are native or non‐native, whether dominance is considered as occurrence or relative abundance, and on variation in mean annual temperature. There were declines in diversity with increasing dominance in invaded communities, but diversity increased with increasing dominance in native communities. These patterns occur along the global temperature gradient. However, positive and negative relationships are strongest in the hottest sites. We also found that climate regulates the degree of behavioral dominance, but differently from how it shapes species richness. Our findings imply that, despite strong competitive interactions among ants, competitive exclusion is not a major driver of local richness in native ant communities. Although the dominance‐impoverishment rule applies to invaded communities, we propose an alternative dominance‐diversification rule for native communities.

Global Island Monitoring Scheme (GIMS): a proposal for the long-term coordinated survey and monitoring of native island forest biota - Paulo A. V. Borges; Pedro Cardoso; Holger Kreft; Robert J. Whittaker; Simone Fattorini; Brent C. Emerson; Artur Gil; Rosemary G. Gillespie; Thomas J. Matthews; Ana M. C. Santos; Manuel J. Steinbauer; Christophe Thébaud; et al. (Biodiversity and Conservation, 2018)

Dietary composition of black drum Pogonias cromis in a hypersaline estuary reflects water quality and prey availability - Kathryn S. Rubio; Matthew Ajemian; Gregory W. Stunz; Terence A. Palmer; Benoit Lebreton; Jennifer Beseres Pollack (Journal of Fish Biology, 2018)
The Baffin Bay estuary is a hypersaline system in the Gulf of Mexico that supports an important recreational and commercial fishery for black drum Pogonias cromis , a benthic predator. Seasonal measurements of water quality variables, benthic macrofauna densities and biomass, and determination of P. cromis food sources using stomach‐content and stable‐isotope analyses were carried out to determine how P. cromis food sources change with water quality and how this may affect P. cromis diet. Gut‐content analysis indicated P. cromis selectively consumed bivalves Mulinia lateralis and Anomalocardia auberiana . Isotope compositions demonstrated that P. cromis relied on these benthic food resources produced in the Baffin Bay estuary year‐round. Biomass and densities of these bivalves were influenced by changes in water quality variables, particularly salinity and dissolved oxygen. Thus, this paper demonstrates the relationship between water quality variables, benthic macrofauna, and their use as food resources by a carnivorous fish species, and emphasizes the need for integrated assessments when studying the effects of water quality on ecosystem function. Holistic approaches such as these can provide important information for management and conservation of fishery resources and can improve predictions of ecosystem response to climate variability.

GSK3β Controls mTOR and Prosurvival Signaling in Neurons - Malgorzata Urbanska; Agata Gozdz; Matylda Macias; Iwona A. Cymerman; Ewa Liszewska; Ilona Kondratiuk; Herman Devijver; Benoit Lechat; Fred Van Leuven; Jacek Jaworski (Molecular Neurobiology, 2018)

Phylogeography, evolutionary history and effects of glaciations in a species ( Zootoca vivipara ) inhabiting multiple biogeographic regions - Jose L. Horreo; Maria L. Pelaez; Teresa Suárez; Merel C. Breedveld; Benoit Heulin; Yann Surget‐Groba; Tuula A. Oksanen; Patrick S. Fitze (Journal of Biogeography, 2018)
Aim During glaciations, the distribution of temperate species inhabiting the Northern Hemisphere generally contracts into southern refugia; and in boreo‐alpine species of the Northern Hemisphere, expansion from Northern refugia is the general rule. Little is known about the drivers explaining vast distributions of species inhabiting multiple biogeographic regions (major biogeographic regions defined by the European Environmental Agency). Here we investigate the fine‐scale phylogeography and evolutionary history of the Eurasian common lizard ( Zootoca vivipara ), the terrestrial reptile with the world's widest and highest latitudinal distribution, that inhabits multiple biogeographic regions. Location Eurasia. Methods We generated the largest molecular dataset to date of Z. vivipara , ran phylogenetic analyses, reconstructed its evolutionary history, determined the location of glacial refuges and reconstructed ancestral biogeographic regions. Results The phylogenetic analyses revealed a complex evolutionary history, driven by expansions and contractions of the distribution due to glacials and interglacials, and the colonization of new biogeographic regions by all lineages of Z. vivipara . Many glacial refugia were detected, most were located close to the southern limit of the Last Glacial Maximum. Two subclades recolonized large areas covered by permafrost during the last glaciation: namely, Western and Northern Europe and North‐Eastern Europe and Asia. Main conclusions In Z. vivipara, most of the glacial refugia were located in the South of their current distribution. Previous studies suggested the existence of Northern refuges, but the species' inability to overwinter on permafrost and the lack of genetic support suggest that the presence of a refugia in the north of the Alps is unlikely. This species currently inhabits boreo‐alpine climates and retracted during previous glaciations into southern refugia, as temperate species. Two clades exhibited enormous geographic expansion that started from two distinct glacial refugia. These phylogeographic patterns were highly congruent with those of Vipera berus . Together they suggest that glacial retraction, the location of the refugia and absence of competition may have promoted the enormous geographic expansion of two clades.

Correction to: Anaphylactoid Reactions to Intravenous N-Acetylcysteine during Treatment for Acetaminophen Poisoning - Mark Yarema; Puja Chopra; Marco L. A. Sivilotti; David Johnson; Alberto Nettel-Aguirre; Benoit Bailey; Charlemaigne Victorino; Sophie Gosselin; Roy Purssell; Margaret Thompson; Daniel Spyker; Barry Rumack (Journal of Medical Toxicology, 2018)

Anaphylactoid Reactions to Intravenous N-Acetylcysteine during Treatment for Acetaminophen Poisoning - Mark Yarema; Puja Chopra; Marco L. A. Sivilotti; David Johnson; Alberto Nettel-Aguirre; Benoit Bailey; Charlemaigne Victorino; Sophie Gosselin; Roy Purssell; Margaret Thompson; Daniel Spyker; Barry Rumack (Journal of Medical Toxicology, 2018)

Directional hydrostratigraphic units simulation using MCP algorithm - N. Benoit; D. Marcotte; A. Boucher; D. D’Or; A. Bajc; H. Rezaee (Stochastic Environmental Research and Risk Assessment, 2018)

Fungal and Bacterial Diversity of Airway Microbiota in Adults with Cystic Fibrosis: Concordance Between Conventional Methods and Ultra-Deep Sequencing, and Their Practical use in the Clinical Laboratory - Françoise Botterel; Cécile Angebault; Odile Cabaret; Franziska A. Stressmann; Jean-Marc Costa; Frédéric Wallet; Benoit Wallaert; Kenneth Bruce; Laurence Delhaes (Mycopathologia, 2018)

Calibration Transfer of a Quantitative Transmission Raman PLS Model: Direct Transfer vs. Global Modeling - Douglas Steinbach; Carl A. Anderson; Gary McGeorge; Benoit Igne; Robert W. Bondi; James K. Drennen (Journal of Pharmaceutical Innovation, 2017)

Prey in oceanic sound scattering layers organize to get a little help from their friends - Kelly J. Benoit‐Bird; Mark A. Moline; Brandon L. Southall (Limnology and Oceanography, 2017)
Group formation in animals is a widespread phenomenon driven by food acquisition, reproduction, and defense. Life in the ocean is characteristically aggregated into horizontally extensive layers as a result of strong vertical gradients in the environment. Each day, animals in high biomass aggregations called “deep scattering layers” migrate vertically, comprising the largest net animal movement on earth. This movement is commonly thought of as a predator avoidance tactic, however, the aggregation of animals into layers has been viewed as an incidental outcome of similar responses by many individuals to the risk of visual predation coupled with the location of resources including food and oxygen rather than active, socially mediated congregation for defense purposes. Here, using a newly adapted autonomous vehicle to measure individual characteristics, we provide the first measures of the internal layer structure, demonstrating that these features are made up of many topologically scaled, mono‐specific aggregations, or “schools” rather than an indiscriminate mix of sizes and species. Schools responded to predators using behavior much like flash compression while neighboring aggregations increased their spacing to maintain coherent layers. Rather than simply an incidental outcome, the formation of layers of life in the sea is a highly organized process driven, at least in part, by biotic pressures for cohesion with broad adaptive significance for the myriad species that inhabit these ubiquitous features. These observations highlight the range of spatial scales we must examine in order to understand the strong impacts these high‐biomass layers have on ecological and biogeochemical processes in the sea.

Nitro-Triarylmethyl Radical as Dual Oxygen and Superoxide Probe - Benoit Driesschaert; Andrey A. Bobko; Valery V. Khramtsov; Jay L. Zweier (Cell Biochemistry and Biophysics, 2017)

Pedigree Reconstruction with Genome-Wide Markers in Potato - Jeffrey B. Endelman; Cari A. Schmitz Carley; David S. Douches; Joseph J. Coombs; Benoit Bizimungu; Walter S. De Jong; Kathleen G. Haynes; David G. Holm; J. Creighton Miller; Richard G. Novy; Jiwan P. Palta; David L. Parish; et al. (American Journal of Potato Research, 2017)

How does a restored oyster reef develop? An assessment based on stable isotopes and community metrics - Ryan J. Rezek; Benoit Lebreton; E. Brendan Roark; Terence A. Palmer; Jennifer Beseres Pollack (Marine Biology, 2017)

Introduction: proceedings of the 2015 New Zealand symposium on algae and photosynthetic prokaryotes - Michael A. Packer; Julian J. Eaton‐Rye; Tina C. Summerfield; Benoit Guieysse; Susanna A. Wood (New Zealand Journal of Botany, 2017)

A global database of ant species abundances - Heloise Gibb; Rob R. Dunn; Nathan J. Sanders; Blair F. Grossman; Manoli Photakis; Silvia Abril; Donat Agosti; Alan N. Andersen; Elena Angulo; Inge Armbrecht; Xavier Arnan; Fabricio B. Baccaro; et al. (Ecology, 2017)
What forces structure ecological assemblages? A key limitation to general insights about assemblage structure is the availability of data that are collected at a small spatial grain (local assemblages) and a large spatial extent (global coverage). Here, we present published and unpublished data from 51 ,388 ant abundance and occurrence records of more than 2,693 species and 7,953 morphospecies from local assemblages collected at 4,212 locations around the world. Ants were selected because they are diverse and abundant globally, comprise a large fraction of animal biomass in most terrestrial communities, and are key contributors to a range of ecosystem functions. Data were collected between 1949 and 2014, and include, for each geo‐referenced sampling site, both the identity of the ants collected and details of sampling design, habitat type, and degree of disturbance. The aim of compiling this data set was to provide comprehensive species abundance data in order to test relationships between assemblage structure and environmental and biogeographic factors. Data were collected using a variety of standardized methods, such as pitfall and Winkler traps, and will be valuable for studies investigating large‐scale forces structuring local assemblages. Understanding such relationships is particularly critical under current rates of global change. We encourage authors holding additional data on systematically collected ant assemblages, especially those in dry and cold, and remote areas, to contact us and contribute their data to this growing data set.

Observed volatilization fluxes of S-metolachlor and benoxacor applied on soil with and without crop residues - C. Bedos; L. Alletto; B. Durand; O. Fanucci; A. Brut; M. Bourdat-Deschamps; S. Giuliano; B. Loubet; E. Ceschia; P. Benoit (Environmental Science and Pollution Research, 2017)

How the truffle got its mate: insights from genetic structure in spontaneous and planted Mediterranean populations of Tuber melanosporum - E. Taschen; F. Rousset; M. Sauve; L. Benoit; M.‐P. Dubois; F. Richard; M.‐A. Selosse (Molecular Ecology, 2016)
The life cycles and dispersal of edible fungi are still poorly known, thus limiting our understanding of their evolution and domestication. The prized Tuber melanosporum produces fruitbodies (fleshy organs where meiospores mature) gathered in natural, spontaneously inoculated forests or harvested in plantations of nursery‐inoculated trees. Yet, how fruitbodies are formed remains unclear, thus limiting yields, and how current domestication attempts affect population genetic structure is overlooked. Fruitbodies result from mating between two haploid individuals: the maternal parent forms the flesh and the meiospores, while the paternal parent only contributes to the meiospores. We analyzed the genetic diversity of T. melanosporum comparatively in spontaneous forests vs. plantations, using SSR polymorphism of 950 samples from South‐East France. All populations displayed strong genetic isolation by distance at the metric scale, possibly due to animal dispersal, meiospore persistence in soil, and/or exclusion of unrelated individuals by vegetative incompatibility. High inbreeding was consistently found, suggesting that parents often develop from meiospores produced by the same fruitbody. Unlike maternal genotypes, paternal mycelia contributed to few fruitbodies each, did not persist over years, and were undetectable on tree mycorrhizae. Thus, we postulate that germlings from the soil spore bank act as paternal partners. Paternal genetic diversity and outbreeding were higher in plantations than in spontaneous truffle‐grounds, perhaps because truffle growers disperse fruitbodies to maintain inoculation in plantations. However, planted and spontaneous populations were not genetically isolated, so that T. melanosporum illustrates an early step of domestication where genetic structure remains little affected.

Habitat availability and geographic isolation as potential drivers of population structure in an oceanic dolphin in the Southwest Indian Ocean - Amélia Viricel; Benoit Simon-Bouhet; Laura Ceyrac; Violaine Dulau-Drouot; Per Berggren; Omar A. Amir; Narriman S. Jiddawi; Philippe Mongin; Jeremy J. Kiszka (Marine Biology, 2016)

There's no place like home: seedling mortality contributes to the habitat specialisation of tree species across Amazonia - Claire Fortunel; C. E. Timothy Paine; Paul V. A. Fine; Italo Mesones; Jean‐Yves Goret; Benoit Burban; Jocelyn Cazal; Christopher Baraloto (Ecology Letters, 2016)
Understanding the mechanisms generating species distributions remains a challenge, especially in hyperdiverse tropical forests. We evaluated the role of rainfall variation, soil gradients and herbivory on seedling mortality, and how variation in seedling performance along these gradients contributes to habitat specialisation. In a 4‐year experiment, replicated at the two extremes of the Amazon basin, we reciprocally transplanted 4638 tree seedlings of 41 habitat‐specialist species from seven phylogenetic lineages among the three most important forest habitats of lowland Amazonia. Rainfall variation, flooding and soil gradients strongly influenced seedling mortality, whereas herbivory had negligible impact. Seedling mortality varied strongly among habitats, consistent with predictions for habitat specialists in most lineages. This suggests that seedling performance is a primary determinant of the habitat associations of adult trees across Amazonia. It further suggests that tree diversity, currently mostly harboured in terra firme forests, may be strongly impacted by the predicted climate changes in Amazonia.

Toluene diisocyanate and methylene diphenyl diisocyanate: asthmatic response and cross-reactivity in a mouse model - Lore Pollaris; Fien Devos; Vanessa De Vooght; Sven Seys; Benoit Nemery; Peter H. M. Hoet; Jeroen A. J. Vanoirbeek (Archives of Toxicology, 2016)

Early Passage Dependence of Mesenchymal Stem Cell Mechanics Influences Cellular Invasion and Migration - Stephen T. Spagnol; Wei-Chun Lin; Elizabeth A. Booth; Benoit Ladoux; Hillard M. Lazarus; Kris Noel Dahl (Annals of Biomedical Engineering, 2016)

Simulations of the flow in the Mahakam river–lake–delta system, Indonesia - Chien Pham Van; Benjamin de Brye; Eric Deleersnijder; A. J. F. Hoitink; Maximiliano Sassi; Benoit Spinewine; Hidayat Hidayat; Sandra Soares-Frazão (Environmental Fluid Mechanics, 2016)

Short day-triggered quiescence promotes water conservation in the American dog tick, Dermacentor variabilis - Jay A. Yoder; Andrew J. Rosendale; Joshua B. Benoit (Journal of Comparative Physiology B, 2016)

The harlequin ladybird, Harmonia axyridis: global perspectives on invasion history and ecology - Helen E. Roy; Peter M. J. Brown; Tim Adriaens; Nick Berkvens; Isabel Borges; Susana Clusella-Trullas; Richard F. Comont; Patrick De Clercq; Rene Eschen; Arnaud Estoup; Edward W. Evans; Benoit Facon; et al. (Biological Invasions, 2016)

Metal binding to the N-terminal cytoplasmic domain of the PIB ATPase HMA4 is required for metal transport in Arabidopsis - Clémentine Laurent; Gilles Lekeux; Ashwinie A. Ukuwela; Zhiguang Xiao; Jean-Benoit Charlier; Bernard Bosman; Monique Carnol; Patrick Motte; Christian Damblon; Moreno Galleni; Marc Hanikenne (Plant Molecular Biology, 2016)

Diguanylate cyclase D gc P is involved in plant and human P seudomonas spp. infections - Isabel M. Aragon; Daniel Pérez‐Mendoza; Joana A. Moscoso; Emmanuel Faure; Benoit Guery; María‐Trinidad Gallegos; Alain Filloux; Cayo Ramos (Environmental Microbiology, 2015)
Summary The second messenger cyclic di‐ GMP (c‐di‐ GMP ) controls the transition between different lifestyles in bacterial pathogens. Here, we report the identification of D gc P (diguanylate cyclase conserved in P seudomonads), whose activity in the olive tree pathogen P seudomonas savastanoi pv. savastanoi is dependent on the integrity of its GGDEF domain. Furthermore, deletion of the dgc P gene revealed that D gc P negatively regulates motility and positively controls biofilm formation in both the olive tree pathogen P . savastanoi pv. savastanoi and the human opportunistic pathogen P seudomonas aeruginosa . Overexpression of the dgc P gene in P . aeruginosa PAK led to increased exopolysaccharide production and upregulation of the type VI secretion system; in turn, it repressed the type III secretion system, which is a hallmark of chronic infections and persistence for P . aeruginosa . Deletion of the dgc P gene in P . savastanoi pv. savastanoi NCPPB 3335 and P . aeruginosa PAK reduced their virulence in olive plants and in a mouse acute lung injury model respectively. Our results show that diguanylate cyclase D gc P is a conserved P seudomonas protein with a role in virulence, and confirm the existence of common c‐di‐ GMP signalling pathways that are capable of regulating plant and human P seudomonas spp. infections.

B acillus subtilis attachment to A spergillus niger hyphae results in mutually altered metabolism - Isabelle Benoit; Marielle H. van den Esker; Aleksandrina Patyshakuliyeva; Derek J. Mattern; Felix Blei; Miaomiao Zhou; Jan Dijksterhuis; Axel A. Brakhage; Oscar P. Kuipers; Ronald P. de Vries; Ákos T. Kovács (Environmental Microbiology, 2015)
Summary Interaction between microbes affects the growth, metabolism and differentiation of members of the microbial community. While direct and indirect competition, like antagonism and nutrient consumption have a negative effect on the interacting members of the population, microbes have also evolved in nature not only to fight, but in some cases to adapt to or support each other, while increasing the fitness of the community. The presence of bacteria and fungi in soil results in various interactions including mutualism. Bacilli attach to the plant root and form complex communities in the rhizosphere. B acillus subtilis , when grown in the presence of A spergillus niger , interacts similarly with the fungus, by attaching and growing on the hyphae. Based on data obtained in a dual transcriptome experiment, we suggest that both fungi and bacteria alter their metabolism during this interaction. Interestingly, the transcription of genes related to the antifungal and putative antibacterial defence mechanism of B . subtilis and A . niger , respectively, are decreased upon attachment of bacteria to the mycelia. Analysis of the culture supernatant suggests that surfactin production by B . subtilis was reduced when the bacterium was co‐cultivated with the fungus. Our experiments provide new insights into the interaction between a bacterium and a fungus.

Formaldehyde Concentration in Discharge from Land Based Aquaculture Facilities in Atlantic Canada - Benoit A. Lalonde; William Ernst; Christine Garron (Bulletin of Environmental Contamination and Toxicology, 2015)

Chemical and physical characterisation of effluents from land-based fish farms in Atlantic Canada - Benoit A. Lalonde; William Ernst; Christine Garron (Aquaculture International, 2015)

Emerging roles of aquaporins in relation to the physiology of blood-feeding arthropods - Joshua B. Benoit; Immo A. Hansen; Elise M. Szuter; Lisa L. Drake; Denielle L. Burnett; Geoffrey M. Attardo (Journal of Comparative Physiology B, 2014)

Stress hormones in relation to breeding status and territory location in colonial king penguin: a role for social density? - Vincent A. Viblanc; Benoit Gineste; Antoine Stier; Jean-Patrice Robin; René Groscolas (Oecologia, 2014)

Habitat‐driven population structure of bottlenose dolphins, T ursiops truncatus , in the N orth‐ E ast A tlantic - Marie Louis; Amélia Viricel; Tamara Lucas; Hélène Peltier; Eric Alfonsi; Simon Berrow; Andrew Brownlow; Pablo Covelo; Willy Dabin; Rob Deaville; Renaud de Stephanis; François Gally; et al. (Molecular Ecology, 2014)
Despite no obvious barrier to gene flow, historical environmental processes and ecological specializations can lead to genetic differentiation in highly mobile animals. Ecotypes emerged in several large mammal species as a result of niche specializations and/or social organization. In the N orth‐ W est A tlantic, two distinct bottlenose dolphin ( T ursiops truncatus ) ecotypes (i.e. ‘coastal’ and ‘pelagic’) have been identified. Here, we investigated the genetic population structure of N orth‐ E ast A tlantic ( NEA ) bottlenose dolphins on a large scale through the analysis of 381 biopsy‐sampled or stranded animals using 25 microsatellites and a 682‐bp portion of the mitochondrial control region. We shed light on the likely origin of stranded animals using a carcass drift prediction model. We showed, for the first time, that coastal and pelagic bottlenose dolphins were highly differentiated in the NEA . Finer‐scale population structure was found within the two groups. We suggest that distinct founding events followed by parallel adaptation may have occurred independently from a large A tlantic pelagic population in the two sides of the basin. Divergence could be maintained by philopatry possibly as a result of foraging specializations and social organization. As coastal environments are under increasing anthropogenic pressures, small and isolated populations might be at risk and require appropriate conservation policies to preserve their habitats. While genetics can be a powerful first step to delineate ecotypes in protected and difficult to access taxa, ecotype distinction should be further documented through diet studies and the examination of cranial skull features associated with feeding.

Seasonal Mercury Dynamics in a New England Vernal Pool - Janina M. Benoit; Deborah A. Cato; Katherine C. Denison; Amy E. Moreira (Wetlands, 2013)

The MISTIGRI thermal infrared project: scientific objectives and mission specifications - Jean-Pierre Lagouarde; Michel Bach; José A. Sobrino; Gilles Boulet; Xavier Briottet; Selma Cherchali; Benoit Coudert; Isabelle Dadou; Gérard Dedieu; Philippe Gamet; Olivier Hagolle; Frédéric Jacob; et al. (International Journal of Remote Sensing, 2013)

Archaeal diversity from hydrothermal systems of Deception Island, Antarctica - Maximiliano J. Amenábar; Patricio A. Flores; Benoit Pugin; Freddy A. Boehmwald; Jenny M. Blamey (Polar Biology, 2013)

Evolutionary history of almond tree domestication in the M editerranean basin - M. Delplancke; N. Alvarez; L. Benoit; A. Espíndola; H. I Joly; S. Neuenschwander; N. Arrigo (Molecular Ecology, 2013)
Genetic diversity of contemporary domesticated species is shaped by both natural and human‐driven processes. However, until now, little is known about how domestication has imprinted the variation of fruit tree species. In this study, we reconstruct the recent evolutionary history of the domesticated almond tree, Prunus dulcis , around the Mediterranean basin, using a combination of nuclear and chloroplast microsatellites [i.e. simple sequence repeat ( SSR s)] to investigate patterns of genetic diversity. Whereas conservative chloroplast SSR s show a widespread haplotype and rare locally distributed variants, nuclear SSR s show a pattern of isolation by distance with clines of diversity from the East to the West of the Mediterranean basin, while Bayesian genetic clustering reveals a substantial longitudinal genetic structure. Both kinds of markers thus support a single domestication event, in the eastern side of the Mediterranean basin. In addition, model‐based estimation of the timing of genetic divergence among those clusters is estimated sometime during the Holocene, a result that is compatible with human‐mediated dispersal of almond tree out of its centre of origin. Still, the detection of region‐specific alleles suggests that gene flow from relictual wild preglacial populations (in North Africa) or from wild counterparts (in the Near East) could account for a fraction of the diversity observed.

Measurement of Oxytetracycline and Emamectin Benzoate in Freshwater Sediments Downstream of Land Based Aquaculture Facilities in the Atlantic Region of Canada - Benoit A. Lalonde; William Ernst; Lyndsay Greenwood (Bulletin of Environmental Contamination and Toxicology, 2012)

A single gene encodes isopentenyl diphosphate isomerase isoforms targeted to plastids, mitochondria and peroxisomes in Catharanthus roseus - Grégory Guirimand; Anthony Guihur; Michael A. Phillips; Audrey Oudin; Gaëlle Glévarec; Céline Melin; Nicolas Papon; Marc Clastre; Benoit St-Pierre; Manuel Rodríguez-Concepción; Vincent Burlat; Vincent Courdavault (Plant Molecular Biology, 2012)

Observations of Thin Layers in Coastal Hawaiian Waters - Margaret A. McManus; Jeff C. Sevadjian; Kelly J. Benoit-Bird; Olivia M. Cheriton; Amanda H. V. Timmerman; Chad M. Waluk (Estuaries and Coasts, 2012)

Analysis of Benthic Invertebrate Communities as a Function of Distance from Two Fish-Processing Plant Effluent Discharges in New Brunswick, Canada - Benoit A. Lalonde; William Ernst (Archives of Environmental Contamination and Toxicology, 2012)

Refining instrument attachment on phocid seals - Iain C. Field; Robert G. Harcourt; Lars Boehme; P. J. Nico de Bruyn; Jean‐Benoit Charrassin; Clive R. McMahon; Marthán N. Bester; Mike A. Fedak; Mark A. Hindell (Marine Mammal Science, 2012)

Disruption of ant-seed dispersal mutualisms by the invasive Asian needle ant (Pachycondyla chinensis) - Mariano A. Rodriguez-Cabal; Katharine L. Stuble; Benoit Guénard; Robert R. Dunn; Nathan J. Sanders (Biological Invasions, 2012)

Multiple traumatic insemination events reduce the ability of bed bug females to maintain water balance - Joshua B. Benoit; Andrew J. Jajack; Jay A. Yoder (Journal of Comparative Physiology B, 2012)

A New Cell for Electrical Conductivity Measurement on Saturated Samples at Upper Crust Conditions - Marie Violay; Benoit Gibert; Pierre Azais; Philippe A. Pezard; Gérard Lods (Transport in Porous Media, 2012)

A Comparative Toxicity Assessment of Materials Used in Aquatic Construction - Benoit A. Lalonde; William Ernst; Gary Julien; Paula Jackman; Ken Doe; Rebecca Schaefer (Archives of Environmental Contamination and Toxicology, 2011)

Trace Metal Concentrations in Sediments and Fish in the Vicinity of Ash Lagoon Discharges from Coal-Combustion Plants in New Brunswick and Nova Scotia, Canada - Benoit A. Lalonde; William Ernst; Fernand Comeau (Archives of Environmental Contamination and Toxicology, 2011)

Functional analysis of the DAT gene promoter using transient Catharanthus roseus and stable Nicotiana tabacum transformation systems - Abdullah Makhzoum; Geneviève Petit-Paly; Benoit St. Pierre; Mark A. Bernards (Plant Cell Reports, 2011)

Increased cave dwelling reduces the ability of cave crickets to resist dehydration - Jay A. Yoder; Joshua B. Benoit; Michael J. LaCagnin; Horton H. Hobbs (Journal of Comparative Physiology B, 2011)

Polybrominated Diphenyl Ethers Concentrations in Fish Processing Plant Effluent - Benoit A. Lalonde; William Ernst (Bulletin of Environmental Contamination and Toxicology, 2010)

Genome-wide profiling of histone H3 lysine 9 acetylation and dimethylation in Arabidopsis reveals correlation between multiple histone marks and gene expression - Junli Zhou; Xiangfeng Wang; Kun He; Jean-Benoit F. Charron; Axel A. Elling; Xing Wang Deng (Plant Molecular Biology, 2010)

Polybrominated Diphenyl Ethers (PBDEs) Concentration in Sediments Located in the Vicinity of Fish Plant Effluent Outfalls in the Maritimes - Benoit A. Lalonde; William Ernst (Bulletin of Environmental Contamination and Toxicology, 2010)

Role of permanent host association with the Madagascar hissing-cockroach, Gromphadorhina portentosa, on the developmental water requirements of the mite, Gromphadorholaelaps schaeferi - J. A. Yoder; B. Z. Hedges; J. B. Benoit; G. D. Keeney (Journal of Comparative Physiology B, 2009)

Dehydration, rehydration, and overhydration alter patterns of gene expression in the Antarctic midge, Belgica antarctica - Giancarlo Lopez-Martinez; Joshua B. Benoit; Joseph P. Rinehart; Michael A. Elnitsky; Richard E. Lee; David L. Denlinger (Journal of Comparative Physiology B, 2009)

Toxicity Testing of Sediment Collected in the Vicinity of Effluent Discharges from Seafood Processing Plants in the Maritimes - Benoit A. Lalonde; Paula Jackman; Ken Doe; Christine Garron; Jamie Aubé (Archives of Environmental Contamination and Toxicology, 2009)

Climatic drivers of hemispheric asymmetry in global patterns of ant species richness - Robert R. Dunn; Donat Agosti; Alan N. Andersen; Xavier Arnan; Carsten A. Bruhl; Xim Cerdá; Aaron M. Ellison; Brian L. Fisher; Matthew C. Fitzpatrick; Heloise Gibb; Nicholas J. Gotelli; Aaron D. Gove; et al. (Ecology Letters, 2009)
Although many taxa show a latitudinal gradient in richness, the relationship between latitude and species richness is often asymmetrical between the northern and southern hemispheres. Here we examine the latitudinal pattern of species richness across 1003 local ant assemblages. We find latitudinal asymmetry, with southern hemisphere sites being more diverse than northern hemisphere sites. Most of this asymmetry could be explained statistically by differences in contemporary climate. Local ant species richness was positively associated with temperature, but negatively (although weakly) associated with temperature range and precipitation. After contemporary climate was accounted for, a modest difference in diversity between hemispheres persisted, suggesting that factors other than contemporary climate contributed to the hemispherical asymmetry. The most parsimonious explanation for this remaining asymmetry is that greater climate change since the Eocene in the northern than in the southern hemisphere has led to more extinctions in the northern hemisphere with consequent effects on local ant species richness.

Influence of agricultural practices on micrometerological spatial variations at local and regional scales - D. Courault; F. Jacob; V. Benoit; M. Weiss; O. Marloie; J. F. Hanocq; E. Fillol; A. Olioso; G. Dedieu; P. Gouaux; M. Gay; A. French (International Journal of Remote Sensing, 2009)

Antarctic Collembolans Use Chemical Signals to Promote Aggregation and Egg Laying - J. B. Benoit; M. A. Elnitsky; G. G. Schulte; R. E. Lee; D. L. Denlinger (Journal of Insect Behavior, 2009)

Regulation of the external mycoflora of the giant Madagascar hissing-cockroach,gromphadorhina portentosa, by its mite associate,gromphadorholaelaps schaeferi, and its implications on human health - Jay A. Yoder; Michael J. Chambers; Michael R. Condon; Joshua B. Benoit; Lawrence W. Zettler (Symbiosis, 2009)

The seabird tick, Ixodes uriae, uses uric acid in penguin guano as a kairomone and guanine in tick feces as an assembly pheromone on the Antarctic Peninsula - Joshua B. Benoit; Giancarlo Lopez-Martinez; Seth A. Philips; Michael A. Elnitsky; Jay A. Yoder; Richard E. Lee; David L. Denlinger (Polar Biology, 2008)

Extremely large aggregations of collembolan eggs on Humble Island, Antarctica: a response to early seasonal warming? - Glen G. Schulte; Michael A. Elnitsky; Joshua B. Benoit; David L. Denlinger; Richard E. Lee (Polar Biology, 2008)

Adaptations for the maintenance of water balance by three species of Antarctic mites - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Polar Biology, 2008)

Dynamic restacking of Escherichia Coli P-pili - Robert A. Lugmaier; Staffan Schedin; Ferdinand Kühner; Martin Benoit (European Biophysics Journal, 2008)

Parasite Prevalence, Abundance, and Diversity in a Semi-free-ranging Colony of Mandrillus sphinx - Joanna M. Setchell; Issa-Ben Bedjabaga; Benoit Goossens; Patricia Reed; E. Jean Wickings; Leslie A. Knapp (International Journal of Primatology, 2007)

Habitat requirements of the seabird tick, Ixodes uriae (Acari: Ixodidae), from the Antarctic Peninsula in relation to water balance characteristics of eggs, nonfed and engorged stages - J. B. Benoit; J. A. Yoder; G. Lopez-Martinez; M. A. Elnitsky; R. E. Lee; D. L. Denlinger (Journal of Comparative Physiology B, 2007)

Towards Positional Cloning in Brassica napus: Generation and Analysis of Doubled Haploid B. rapa Possessing the B. napus pol CMS and Rfp Nuclear Restorer Gene - Nataša Formanová; Xiu-Qing Li; Alison M. R. Ferrie; Mary DePauw; Wilf A. Keller; Benoit Landry; Gregory G. Brown (Plant Molecular Biology, 2006)

Genomics of hybrid poplar ( Populus trichocarpa × deltoides ) interacting with forest tent caterpillars ( Malacosoma disstria ): normalized and full‐length cDNA libraries, expressed sequence tags, and a cDNA microarray for the study of insect‐induced defences in poplar - STEVEN RALPH; CLAIRE ODDY; DAWN COOPER; HESTHER YUEH; SHARON JANCSIK; NATALIA KOLOSOVA; RYAN N. PHILIPPE; DANA AESCHLIMAN; RICK WHITE; DEZENE HUBER; CAROL E. RITLAND; FRANÇOIS BENOIT; et al. (Molecular Ecology, 2006)
As part of a genomics strategy to characterize inducible defences against insect herbivory in poplar, we developed a comprehensive suite of functional genomics resources including cDNA libraries, expressed sequence tags (ESTs) and a cDNA microarray platform. These resources are designed to complement the existing poplar genome sequence and poplar ( Populus spp.) ESTs by focusing on herbivore‐ and elicitor‐treated tissues and incorporating normalization methods to capture rare transcripts. From a set of 15 standard, normalized or full‐length cDNA libraries, we generated 139 007 3′‐ or 5′‐end sequenced ESTs, representing more than one‐third of the c. 385 000 publicly available Populus ESTs. Clustering and assembly of 107 519 3′‐end ESTs resulted in 14 451 contigs and 20 560 singletons, altogether representing 35 011 putative unique transcripts, or potentially more than three‐quarters of the predicted c. 45 000 genes in the poplar genome. Using this EST resource, we developed a cDNA microarray containing 15 496 unique genes, which was utilized to monitor gene expression in poplar leaves in response to herbivory by forest tent caterpillars ( Malacosoma disstria ). After 24 h of feeding, 1191 genes were classified as up‐regulated, compared to only 537 down‐regulated. Functional classification of this induced gene set revealed genes with roles in plant defence (e.g. endochitinases, Kunitz protease inhibitors), octadecanoid and ethylene signalling (e.g. lipoxygenase, allene oxide synthase, 1‐aminocyclopropane‐1‐carboxylate oxidase), transport (e.g. ABC proteins, calreticulin), secondary metabolism [e.g. polyphenol oxidase, isoflavone reductase, (–)‐germacrene D synthase] and transcriptional regulation [e.g. leucine‐rich repeat transmembrane kinase, several transcription factor classes (zinc finger C3H type, AP2/EREBP, WRKY, bHLH)]. This study provides the first genome‐scale approach to characterize insect‐induced defences in a woody perennial providing a solid platform for functional investigation of plant–insect interactions in poplar.

A high blood lactate induced by heavy exercise does not affect the increase in submaximal $$\dot V{\text{O}}_2 $$ with hyperoxia - F. B. Favier; F. Prieur; O. Grataloup; T. Busso; J. Castells; C. Denis; A. Geyssant; H. Benoit (European Journal of Applied Physiology, 2005)

An EST resource for cassava and other species of Euphorbiaceae - James V. Anderson; Michel Delseny; Martin A. Fregene; Veronique Jorge; Chikelu Mba; Camilo Lopez; Silvia Restrepo; Mauricio Soto; Benoit Piegu; Valerie Verdier; Richard Cooke; Joe Tohme; et al. (Plant Molecular Biology, 2004)

Water relations in eggs of the lone star tick, Amblyomma americanum, with experimental work on the capacity for water vapor absorption - Jay A. Yoder; Joshua B. Benoit; Amanda M. Opaluch (Experimental and Applied Acarology, 2004)

Response of Avian Communities to Historic Habitat Change in the Northern Chihuahuan Desert - A. M. Pidgeon; N. E. Mathews; R. Benoit; E. V. Nordheim (Conservation Biology, 2001)
Throughout much of the northern Chihuahuan Desert, the grasslands that were widespread at the time of European settlement have been replaced by desert shrublands. Little is known about the effects of this change on avian communities. We analyzed historic U.S. Government Land Office records to assess large‐scale changes in vegetation cover from the 1880s to the present day. We studied vegetation and avian communities in one grassland habitat type and four desert shrubland habitat types to examine (1) how breeding‐bird communities may have changed in response to habitat conversion from grassland to desert shrubland and (2) whether breeding‐bird communities differ among the four desert shrubland habitat types that compose Chihuahuan Desert scrub in this region. To estimate the characteristics of 1880s black grama ( Bouteloua eriopoda ) grassland, we focused on plots located within extensive patches of present‐day black grama and compared the avian communities found there with those in desert shrubland. Species richness was higher in desert shrubland than grassland. Among the desert shrubland habitat types, species richness was consistently highest in mesquite. Avian abundance patterns differed among the four desert shrubland habitat types. At least 30% of the avian community in each habitat pair was distinct. Conversion of grassland to shrubland in south‐central New Mexico has likely been accompanied by a major turnover in the avian community. Remaining tracts of black grama provide habitat for species that may be uniquely adapted to the northern Chihuahuan Desert and should be protected.

Framework for modelling data uncertainty in life cycle inventories - Mark A. J. Huijbregts; Gregory Norris; Rolf Bretz; Andreas Ciroth; Benoit Maurice; Bo von Bahr; Bo Weidema; Angeline S. H. de Beaufort (The International Journal of Life Cycle Assessment, 2001)

Neurons in the posteromedial lateral suprasylvian area of the cat are sensitive to binocular positional depth cues - Benoit A. Bacon; Franco Lepore; Jean-Paul Guillemot (Experimental Brain Research, 2000)

Effects of zopiclone on the rest/activity rhythm after a westward flight across five time zones - A. Daurat; O. Benoit; A. Buguet (Psychopharmacology, 2000)

A Simulation Tool for Industrial Ecology: Creating a Board Game - Benoit Cushman‐Roisin; Norman J. Rice III; Michael A. Moldaver (Journal of Industrial Ecology, 1999)
Summary This article presents a board game that was developed for use as a simulation tool in teaching the basic concepts of industrial ecology (IE). The game, with the automobile industry as its theme, includes realistic numbers and displays a variety of IE principles. The objectives of the simulation, however, transcend the automobile industry and apply to other manufacturing industries. They include: pollution prevention, design for environment (in several forms, including design for disassembly), environmental management, and life‐cycle assessment. The game has already been played by engineering and business professors, graduate students in environmental engineering, government representatives, and industry executives. A statistical analysis performed on pre‐ and post‐game questionnaires indicates that the game is an effective teaching tool.

Impact of the spread ofPhragmites on the distribution of birds in Connecticut tidal marshes - Lori K. Benoit; Robert A. Askins (Wetlands, 1999)

Binocular interactions and spatial disparity sensitivity in the superior colliculus of the siamese cat - Benoit A. Bacon; Franco Lepore; Jean-Paul Guillemot (Experimental Brain Research, 1999)

A system to simulate gas exchange in humans to control quality of metabolic measurements - F. Prieur; T. Busso; J. Castells; R. Bonnefoy; H. Benoit; A. Geyssant; C. Denis (European Journal of Applied Physiology, 1998)

Accuracy of pulse oximetry during intense exercise under severe hypoxic conditions - H. Benoit; F. Costes; L. Feasson; J. R. Lacour; F. Roche; C. Denis; A. Geyssant; J. C. Barthlmy (European Journal of Applied Physiology, 1997)

Life cycle and behavioural assessments of the influence of substrate particle size on Chironomus tentans (Diptera: Chironomidae) in laboratory assays - Paul K. Sibley; Duane A. Benoit; Gerald T. Ankley (Hydrobiologia, 1997)

Effects of fertilizer on insecticides adsorption and biodegradation in crop soils - J. Rouchaud; A. Thirion; A. Wauters; F. Van de Steene; F. Benoit; N. Ceustermans; J. Gillet; S. Marchand; L. Vanparys (Archives of Environmental Contamination and Toxicology, 1996)